resin composition
Patent Information
- Application Number
- JP2026041906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-16
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167528000001 
Figure 2026167528000002 
Figure 2026167528000003
Abstract
Description
[Technical Field]
[0001] This invention relates to a resin composition. Furthermore, it relates to a resin sheet, a cured product, a circuit board, and a semiconductor device obtained using the resin composition. [Background technology]
[0002] Resin compositions containing epoxy resins have been widely used as insulating materials for circuit boards such as printed circuit boards and redistribution boards for semiconductor packages because they produce cured products with excellent insulating properties.
[0003] On the other hand, with the recent increase in communication speed and the sophistication of circuit boards, insulating materials for circuit boards require insulating materials with excellent dielectric properties (low dielectric loss tangent) to reduce transmission loss when operating in high-frequency environments. As insulating materials with excellent dielectric properties, there have been reports of using specific curing agents, such as active ester resins, that can reduce or suppress the generation of polar groups such as secondary hydroxyl groups during the curing reaction of epoxy resins, and also using maleimide resins (for example, Patent Document 1). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2010-90238 [Overview of the project] [Problems that the invention aims to solve]
[0005] The inventors have confirmed that when maleimide resin is used in combination with a resin composition containing epoxy resin and activated ester resin, excellent dielectric properties (dielectric loss tangent) and excellent adhesion to the underlying copper (adhesion to the underlying copper) can be achieved in insulating layers of a certain thickness or greater. However, in thin films of 30 μm or less, the dielectric properties deteriorate, and it can be difficult to achieve low dielectric loss tangent in thin films. Furthermore, the inventors have confirmed that while a cured product exhibiting excellent dielectric loss tangent can be obtained even in thin films by using a phenolic resin having nitrogen atoms such as a triazine skeleton, the film stability may deteriorate because the nitrogen atom portion of the triazine skeleton can act catalytically.
[0006] The present invention has been made in view of the above problems, and aims to provide a resin composition that exhibits excellent dielectric properties (low dielectric loss tangent) even in thin films, produces a cured product with excellent adhesion to the underlying copper, and has high film stability. [Means for solving the problem]
[0007] As a result of diligent research by the present inventors, they have found that the above problems can be solved by a resin composition containing (A) epoxy resin, (B) active ester resin, (C) maleimide resin, (D) phenol resin (excluding those having a triazine skeleton), and (E) inorganic filler, wherein component (C) is a maleimide resin having (C1) aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and a maleimide resin having (C2) no aromatic rings, or having aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of more than 0.25, and have completed the present invention.
[0008] In other words, the present invention includes the following: <1> (A) Epoxy resin, (B) Active ester resin, (C) Maleimide resin, (D) Phenolic resins (excluding those having a triazine skeleton), and (E) Inorganic filler, A resin composition containing, A resin composition comprising: (C) a maleimide resin having an aromatic ring (C1) and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less; and (C2) a maleimide resin that does not have an aromatic ring, or has an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of more than 0.25. <2> The ratio of the total number of moles of active groups in component (B) to the total number of moles of active groups in component (A) [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] is 1.9 or less. <1> The resin composition described above. <3> The ratio of the total number of moles of active groups in component (B) to the total number of moles of active groups in component (A) [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] is 1.2 or greater. <1> or <2> The resin composition described above. <4> The content of component (C) is 1 to 15% by mass, when the non-volatile components in the resin composition are considered to be 100% by mass. <1> ~ <3> A resin composition as described in any of the following. <5> The mass ratio of component (C1) to component (C2) [(C1) component / (C2) component] is between 0.1 and 100. <1> ~ <4> A resin composition as described in any of the following. <6> Component (C2) contains a maleimide resin represented by the following formula (C2-1): <1> ~ <5> A resin composition as described in any of the following. [ka] (In the formula, n represents a non-negative integer, and * represents a combination.) <7> (D) Component has an aromatic ring other than the phenol skeleton, <1> ~ <6> A resin composition as described in any of the following. <8> (D) Component has two or more phenolic hydroxyl groups in one molecule. <1> ~ <7> A resin composition as described in any of the following. <9> (D) Component does not have an alkyl group with 3 or more carbon atoms. <1> ~ <8> A resin composition as described in any of the following. <10> (D) Component is a phenol resin whose constituent atoms are selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. <1> ~ <9> A resin composition as described in any of the following. <11> (D) Component is a phenolic resin whose constituent atoms are carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. <1> ~ <10> A resin composition as described in any of the following. <12> The content of component (D) is 0.1 to 10% by mass, when the non-volatile components in the resin composition are considered to be 100% by mass. <1> ~ <11> A resin composition as described in any of the following. <13> Furthermore, (G) containing organic fillers, <1> ~ <12> A resin composition as described in any of the following. <14> Furthermore, (H) contains thermoplastic resin, <1> ~ <13> A resin composition as described in any of the following. <15> Furthermore, (I) containing a curing accelerator, <1> ~ <14> A resin composition as described in any of the following. <16> It is for the insulating layer of a circuit board. <1> ~ <15> A resin composition as described in any of the following. <17> A support and provided on the support <1> ~ <16> A resin sheet comprising a layer of the resin composition described in any of the following. <18> The support is a thermoplastic resin film or a metal foil. <17> The resin sheet described above. <19> <1> ~ <16> A cured product of any of the resin compositions described above. <20> <1> ~ <16> A circuit board comprising an insulating layer having a cured product of any of the resin compositions described above. <21> <20> A semiconductor device including the circuit board described above. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a resin composition that exhibits excellent dielectric properties (low dielectric loss tangent) even in thin films, yields a cured product with excellent adhesion to a copper substrate, and has high film stability, as well as a resin sheet, cured product, circuit board, and semiconductor device obtained using the resin composition. [Modes for carrying out the invention]
[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples listed below, and may be implemented with modifications as appropriate without departing from the scope of the claims and their equivalents.
[0011] [Explanation of terms] In the following explanation, the notations "XX or greater and YY or less" or "XX~YY" that represent numerical ranges mean a numerical range that includes the lower and upper limits, unless otherwise specified. When numerical ranges are described in steps, the upper and lower limits of each numerical range can be combined in any way.
[0012] In the following explanation, "non-volatile components" refers to the components of the resin composition other than the organic solvents described later. Furthermore, "resin components" refers to the non-volatile components of the resin composition, excluding the inorganic fillers described later.
[0013] In the following description, "aromatic ring" refers to a ring that obeys Hückel's rule, where the number of electrons in the π-electron system on the ring is 4r+2 (where r is a natural number), and includes monocyclic aromatic rings and fused aromatic rings formed by the fusion of two or more monocyclic aromatic rings. Unless otherwise specified, monocyclic aromatic rings are preferred as aromatic rings. Aromatic rings can be aromatic carbocyclic rings having only carbon atoms as ring constituent atoms, or aromatic heterocyclic rings having heteroatoms such as oxygen, nitrogen, or sulfur atoms in addition to carbon atoms as ring constituent atoms. Unless otherwise specified, aromatic carbocyclic rings are preferred as aromatic rings. Unless otherwise specified, the number of carbon atoms in an aromatic ring is preferably 3 or more, more preferably 4 or more or 5 or more, and even more preferably 6 or more, with an upper limit of preferably 24 or less, more preferably 18 or less or 14 or less, and even more preferably 10 or less. The number of carbon atoms of substituents is not included in the number of carbon atoms.
[0014] Examples of monocyclic aromatic rings include benzene rings, furan rings, thiophene rings, pyrrole rings, pyrazole rings, oxazole rings, isoxazole rings, furazan rings, thiazole rings, isothiazole rings, thiadiazole rings, imidazole rings, triazole rings, tetrazole rings, pyridine rings, pyridazine rings, pyrimidine rings, pyrazine rings, and pyridazine rings. Examples of condensed aromatic rings formed by the fusion of two or more monocyclic aromatic rings include naphthalene rings, anthracene rings, phenanthrene rings, benzofuran rings, isobenzofuran rings, indole rings, isoindole rings, benzothiophene rings, benzimidazole rings, indazole rings, benzoxazole rings, benzoisoxazole rings, benzothiazole rings, quinoline rings, isoquinoline rings, quinoxaline rings, acridine rings, quinazoline rings, sinnoline rings, phthalazine rings, pyridothiazole rings, benzotriazole rings, imidazopyridine rings, triazopyridine rings, and purine rings. Unless otherwise specified, benzene rings or naphthalene rings are preferred as aromatic rings, with benzene rings being more preferred.
[0015] [Resin composition] The resin composition of the present invention comprises (A) epoxy resin, (B) active ester resin, (C) maleimide resin, (D) phenol resin (excluding those having a triazine skeleton), and (E) inorganic filler, wherein component (C) includes (C1) a maleimide resin having aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and (C2) a maleimide resin that does not have aromatic rings, or has aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of greater than 0.25. By combining components (A), (B), (C1), (C2), (D), and (E) in the resin composition, it is possible to obtain a cured product that exhibits excellent dielectric properties (low dielectric loss tangent) even in thin films, has excellent adhesion to the copper substrate, and improves film stability. The inventors have also confirmed that the cured product produced by this invention exhibits a low dielectric loss tangent even in high-temperature (90°C) environments, has a low rate of increase in dielectric loss tangent when the thickness of the insulating layer (cured product) is reduced, and shows excellent adhesion to the underlying copper even when exposed to high-temperature and high-humidity environments.
[0016] In one embodiment, the resin composition of the present invention is a resin composition comprising (A) an epoxy resin, (B) an active ester resin, (C) a maleimide resin, (D) a phenol resin whose constituent atoms are selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms, and (E) an inorganic filler, wherein component (C) preferably comprises (C1) a maleimide resin having aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and (C2) a maleimide resin that does not have aromatic rings, or has aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of more than 0.25.
[0017] The resin composition of the present invention may contain any additional components in combination with components (A), (B), (C), (D), and (E). Examples of optional components include curing agents other than component (B) or (D) (hereinafter referred to as "(F) other curing agents"), (G) organic fillers, (H) thermoplastic resins, (I) curing accelerators, (J) organic solvents, (K) other additives, etc. The components contained in the resin composition of the present invention will be described in detail below.
[0018] <(A) Epoxy resin> The resin composition of the present invention contains (A) epoxy resin. The epoxy resin is a curable resin having epoxy groups and an epoxy equivalent of 5,000 g / eq. or less. By containing (A) epoxy resin in combination with (B) active ester resin, which will be described later, the resin composition can produce a cured product with excellent adhesion to the copper substrate while maintaining a low dielectric loss tangent Df. (A) epoxy resin may be used alone or in combination of two or more types. In one embodiment, it is preferable to use two or more types of (A) epoxy resin in combination.
[0019] (A) The epoxy resin is not particularly limited in type, as long as it has one or more (preferably two or more) epoxy groups in one molecule. (A) Examples of epoxy resins include bixylenol type epoxy resin, bisphenol type epoxy resin (bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol C type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, etc.), dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, biphenyl aralkyl type Examples include epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiroring-containing epoxy resins, cyclohexane-type epoxy resins, cyclohexanedimethanol-type epoxy resins, naphthylene ether-type epoxy resins, trimethylol-type epoxy resins, tetraphenylethane-type epoxy resins, isocyanurate-type epoxy resins, phenolphthaleimidine-type epoxy resins, glycirol-type epoxy resins, alkylene oxy-backbone-containing epoxy resins, fluorene-structure-containing epoxy resins, halogenated epoxy resins, resorcinol-type epoxy resins, etc. Bisphenol-type epoxy resins, naphthalene-type epoxy resins, or biphenyl-type epoxy resins are preferred, and naphthalene-type epoxy resins or biphenyl-type epoxy resins are more preferred. In one embodiment, component (A) preferably includes an epoxy resin having an aromatic backbone.
[0020] The resin composition of the present invention preferably contains an epoxy resin having two or more epoxy groups in one molecule as component (A). From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of epoxy resin (A) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0021] (A) Epoxy resins include epoxy resins that are liquid at 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at 20°C (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resin as component (A), only solid epoxy resin, or a combination of liquid epoxy resin and solid epoxy resin. In one embodiment, the resin composition of the present invention preferably contains a combination of liquid epoxy resin and solid epoxy resin.
[0022] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.
[0023] Examples of liquid epoxy resins include glycirol-type epoxy resins, bisphenol-type epoxy resins (bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol C-type epoxy resins, bisphenol AF-type epoxy resins, etc.), naphthalene-type epoxy resins, glycidyl ester-type epoxy resins, glycidylamine-type epoxy resins, phenol novolac-type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexanedimethanol-type epoxy resins, cyclic aliphatic glycidyl ethers, epoxy resins having a butadiene structure, dicyclopentadiene-type epoxy resins, alkylene oxy-skeleton-containing epoxy resins, fluorene-containing epoxy resins, and resorcinol-type epoxy resins. Bisphenol-type epoxy resins or naphthalene-type epoxy resins are preferred, and naphthalene-type epoxy resins are more preferred.
[0024] Specific examples of liquid epoxy resins include "EX-992L" from Nagase ChemteX, "YX7400" from Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP-4032SS" (naphthalene-type epoxy resin) from DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epicoat 828EL" from Mitsubishi Chemical Corporation; and "850S" (bisphenol A-type epoxy resin) from DIC Corporation; as well as "jER" from Mitsubishi Chemical Corporation. 807, 1750 (Bisphenol F type epoxy resin); Mitsubishi Chemical's "jER152" (Phenol novolac type epoxy resin); Mitsubishi Chemical's "630", "630LSD", "604" (Glycidylamine type epoxy resin); ADEKA's "ED-523T" (Glysilol type epoxy resin); ADEKA's "EP-3950L", "EP-3980S" (Glycidylamine type epoxy resin); ADEKA's "EP-40 88S (dicyclopentadiene type epoxy resin); "ZX-1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Co., Ltd.; "EX-991L" (alkylene oxy skeleton-containing epoxy resin) manufactured by Nagase ChemteX Co., Ltd.; "Celoxide 2021P" (alicyclic epoxy resin with ester skeleton) manufactured by Daicel Corporation. Examples include: resins; "PB-3600" from Daicel Corporation; "JP-100" and "JP-200" from Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" from Nippon Steel Chemical & Material Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resins); "EG-280" from Osaka Gas Chemical Co., Ltd. (fluorene structure-containing epoxy resin); and "EX-201" from Nagase ChemteX Corporation (resorcinol type epoxy resin). These may be used individually or in combination of two or more types.
[0025] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups per molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups per molecule is more preferred.
[0026] Examples of solid epoxy resins include bixylenol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, triphenylmethane-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, biphenyl aralkyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol-type epoxy resins (bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, etc.), phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, phenolphthaleimidine-type epoxy resins, and fluorene structure-containing epoxy resins. Biphenyl aralkyl-type epoxy resins or biphenyl-type epoxy resins are preferred, and biphenyl-type epoxy resins are more preferred.
[0027] Specific examples of solid epoxy resins include, for example, DIC's "HP4032H" (naphthalene-type epoxy resin); DIC's "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resins); DIC's "N-690" and "N-695" (cresol novolac-type epoxy resins); DIC's "HP-7200," "HP-7200HH," "HP-7200H," and "HP-7200L" (dicyclopentadiene-type epoxy resins); and DIC's "EXA-7311," "EXA-7311-G3," and "EXA-7311-G4." "EXA-7311-G4S", "HP-6000", "HP-6000L" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-3000", "NC-3000L", "NC-3000FH", "NC-3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-3000H" (biphenyl aralkyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "ESN4" manufactured by Nippon Steel Chemical & Material Co., Ltd. 75V", "ESN4100V" (naphthalene-type epoxy resin); "ESN485" (naphthol-type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene-type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL6121" (biphenyl-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX8800" (anthracene-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; Examples include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" from Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) from Mitsubishi Chemical Corporation; "YL7800" (fluorene structure-containing epoxy resin) from Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) from Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) from Mitsubishi Chemical Corporation; and "WHR991S" (phenolphthaleinidine type epoxy resin) from Nippon Kayaku Co., Ltd.These may be used individually or in combination of two or more types.
[0028] (A) The epoxy equivalent of the epoxy resin is preferably 50 to 5,000 g / eq. The lower limit of the epoxy equivalent is preferably 50 g / eq. or more, more preferably 60 g / eq. or more, even more preferably 80 g / eq. or more, and particularly preferably 110 g / eq. or more, as mentioned above. The upper limit of the epoxy equivalent is preferably 5,000 g / eq. or less, more preferably 3,000 g / eq. or less, even more preferably 2,000 g / eq. or less, even more preferably 1,000 g / eq. or less, and particularly preferably 500 g / eq. or less, 400 g / eq. or less, or 300 g / eq. or less. The epoxy equivalent is the mass of the epoxy resin containing one equivalent of epoxy groups and can be measured according to JIS K7236.
[0029] (A) The weight-average molecular weight (Mw) of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight-average molecular weight (Mw) of the epoxy resin can be measured as a polystyrene equivalent value by the GPC method.
[0030] The content of (A) epoxy resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more or 1% by mass or more, even more preferably 2% by mass or more or 3% by mass or more, and particularly preferably 4% by mass or more or 5% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 6% by mass or more. The upper limit is preferably 40% by mass or less or 35% by mass or less, more preferably 30% by mass or less or 25% by mass or less, even more preferably 20% by mass or less, 15% by mass or less or 12% by mass or less, and particularly preferably 10% by mass or less, 9% by mass or less or 8% by mass or less.
[0031] The content of (A) epoxy resin in the resin composition is preferably 1% by mass or 3% by mass or more, more preferably 5% by mass or 8% by mass or more, even more preferably 10% by mass or 12% by mass or more, and particularly preferably 15% by mass or more, 18% by mass or more, or 20% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 22% by mass or more, 24% by mass or more, etc. The upper limit is preferably 70% by mass or less or 65% by mass or less, more preferably 60% by mass or less or 55% by mass or less, even more preferably 50% by mass or less or 45% by mass or less, and particularly preferably 40% by mass or less, 35% by mass or less, or 30% by mass or less. In one embodiment, it may be 28% by mass or less, 26% by mass or less, etc.
[0032] <(B) Active ester resin> The resin composition of the present invention contains (B) an activated ester resin. By containing (B) an activated ester resin in the resin composition, the dielectric loss tangent of the cured product can be effectively reduced. (B) an activated ester resin may be used alone or in combination of two or more types.
[0033] (B) As the active ester resin, compounds having one or more active ester groups in one molecule can be used. Among these, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferred as the active ester resin. The active ester resin is preferably obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. In one embodiment, the active ester resin may be an active ester resin obtained from a carboxylic acid compound and a phenol compound or a naphthol compound, or an active ester resin obtained from a carboxylic acid compound and a phenol compound and a naphthol compound.
[0034] Examples of carboxylic acid compounds include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0035] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, phenylphenol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, and phenol novolac. Here, "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by the condensation of two molecules of phenol with one molecule of dicyclopentadiene.
[0036] (B) Preferred specific examples of active ester resins include active ester resins containing a dicyclopentadiene-type diphenol structure (hereinafter also referred to as "dicyclopentadiene-type active ester resin"), active ester resins containing a naphthalene structure, phosphorus-containing active ester resins, active ester resins containing acetylated phenol novolacs, active ester resins containing benzoylated phenol novolacs, and active ester resins containing a butadiene structure. Among these, active ester resins containing a naphthalene structure, active ester resins containing a dicyclopentadiene-type diphenol structure, or active ester resins containing a butadiene structure are preferred, active ester resins containing a naphthalene structure or active ester resins containing a dicyclopentadiene-type diphenol structure are more preferred, and active ester resins containing a dicyclopentadiene-type diphenol structure are even more preferred. "Dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.
[0037] (B) The active ester group equivalent (functional group equivalent) of the active ester resin is preferably 180 g / eq. or more, more preferably 190 g / eq. or more, even more preferably 200 g / eq. or more, and particularly preferably 210 g / eq. or more. The upper limit of the equivalent amount of the active ester group equivalent (functional group equivalent) can be, for example, 1,000 g / eq. or less, 750 g / eq. or less, 700 g / eq. or less, 600 g / eq. or less, 500 g / eq. or less, 400 g / eq. or less, or 300 g / eq. or less.
[0038] (B) Commercially available active ester resins include: Active ester resins containing a dicyclopentadiene-type diphenol structure such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "EXB-8000H", "HPC-8000L-65MT", "EXB-8000L-65TM" (manufactured by DIC); Naphthalene-type active ester resins containing a naphthalene structure such as "EXB-9416-70BK", "EXB-8100L-65T", "EXB-8150L-65T", "HPC-8150-62T", "EXB-8100L-65T", "E Examples include "XB-8" (manufactured by DIC Corporation), "PC1300-02-65T", "PC1300-02-65MA" (manufactured by Air Water Corporation); "EXB-9401" (manufactured by DIC Corporation) as a phosphorus-containing active ester resin; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester resin containing acetylated phenol novolac; and "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and "EXB-8500-65T" (manufactured by DIC Corporation) as active ester resins that are benzoylated phenol novolacs.
[0039] The content of (B) active ester resin in the resin composition is preferably 1% by mass or more or 2% by mass or more, more preferably 3% by mass or more or 4% by mass or more, even more preferably 5% by mass or more, 6% by mass or more or 7% by mass or more, and particularly preferably 8% by mass or more, 9% by mass or more or 10% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention significantly, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even in a high temperature (90°C) environment. In one embodiment, it may be 11% by mass or more. The upper limit is preferably 40% by mass or less or 35% by mass or less, more preferably 30% by mass or less or 25% by mass or less, even more preferably 20% by mass or less or 18% by mass or less, and particularly preferably 15% by mass or less or 13% by mass or less, from the viewpoint of obtaining a cured product that exhibits even better adhesion to the substrate copper even when exposed to a high temperature and high humidity environment.
[0040] The content of (B) active ester resin in the resin composition is preferably 5% by mass or more or 10% by mass or more, more preferably 15% by mass or more or 20% by mass or more, even more preferably 25% by mass or more or 30% by mass or more, and particularly preferably 35% by mass or more or 38% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention significantly, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even in a high temperature (90°C) environment. In one embodiment, it may be 40% by mass or more, 42% by mass or more, 44% by mass or more, etc. The upper limit is preferably 90% by mass or less or 85% by mass or less, more preferably 80% by mass or less or 75% by mass or less, even more preferably 70% by mass or less or 65% by mass or less, and particularly preferably 60% by mass or less or 55% by mass or less, from the viewpoint of obtaining a cured product that exhibits even better adhesion to the substrate copper even when exposed to a high temperature and high humidity environment. In one embodiment, the amount may be 52% by mass or less, 50% by mass or less, 48% by mass or less, etc.
[0041] The total content of (A) epoxy resin and (B) active ester resin in the resin composition is preferably 2% by mass or more, more preferably 5% by mass or more or 8% by mass or more, even more preferably 10% by mass or more or 12% by mass or more, and particularly preferably 15% by mass or more or 18% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 60% by mass or less or 55% by mass or less, more preferably 50% by mass or less or 45% by mass or less, even more preferably 40% by mass or less or 35% by mass or less, and particularly preferably 30% by mass or less or 25% by mass or less. In one embodiment, it may be 22% by mass or less, 20% by mass or less, etc.
[0042] The total content of (A) epoxy resin and (B) active ester resin in the resin composition, when the total resin component in the resin composition is considered as 100% by mass, is preferably 20% by mass or 25% by mass or more, more preferably 30% by mass or 35% by mass or more, even more preferably 40% by mass or 45% by mass or more, and particularly preferably 50% by mass or more, 55% by mass or more, or 60% by mass or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 65% by mass or more, 70% by mass or more, etc. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less. In one embodiment, it may be 75% by mass or less, etc.
[0043] The mass ratio of component (B) to component (A) in the resin composition [(B) component / (A) component] is preferably 0.1 or higher, more preferably 0.3 or higher or 0.5 or higher, even more preferably 0.8 or higher or 1.0 or higher, and particularly preferably 1.2 or higher or 1.4 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.5 or higher, 1.6 or higher, 1.7 or higher, 1.8 or higher, etc. The upper limit is preferably 10 or lower, more preferably 8 or lower or 6 or lower, even more preferably 5 or lower or 4 or lower, and particularly preferably 3.0 or lower or 2.8 or lower. In one embodiment, it may be 2.5 or lower, 2.2 or lower, 2.0 or lower, 1.9 or lower, etc.
[0044] The ratio of the total number of moles of active groups (active ester groups) of component (B) to the total number of moles of active groups (epoxy groups) of component (A) in the resin composition [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is preferably 0.1 or more or 0.3 or more, more preferably 0.5 or more or 0.8 or more, even more preferably 1.0 or more or 1.1 or more, and particularly preferably 1.2 or more, from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even in a high temperature (90°C) environment. In one embodiment, it may be 1.3 or more, 1.4 or more, etc. The upper limit is preferably 10 or less or 8 or less, more preferably 5 or less or 4 or less, even more preferably 3.0 or less, 2.8 or less, 2.5 or less, 2.2 or less or 2.0 or less, and particularly preferably 1.9 or less, from the viewpoint of obtaining a cured product that exhibits even better adhesion to the substrate copper even when exposed to a high temperature and high humidity environment. In one embodiment, the values may be 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, etc.
[0045] (C) Maleimide resin The resin composition of the present invention contains (C) maleimide resin. As described below, in the present invention, two or more types of (C) maleimide resin are used in combination.
[0046] (C) The type of maleimide resin is not particularly limited, as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrole-1-yl groups) per molecule. Examples of maleimide resins include "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all from Designer Molecules). Maleimide resins containing a 36-carbon aliphatic skeleton derived from dimeramine (manufactured by Inc., etc.); aliphatic maleimide resins such as "SLK-1500-T80" (manufactured by Shin-Etsu Chemical Co., Ltd.), "SLK-6895" (manufactured by Shin-Etsu Chemical Co., Ltd.), and "BMI-TMH" (manufactured by Yamato Kasei Co., Ltd.); maleimide resins containing an indan skeleton as described in the Japan Institute of Invention and Innovation, Technical Report No. 2020-500211; maleimide resins containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT", "MIR-5000-60T" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000", "BMI-2300" (manufactured by Yamato Kasei Co., Ltd.), "BMI-80", and "BMI-70" (manufactured by Kei-I Kasei Co., Ltd.); "BMI-4200" (Designer Molecules Examples include maleimide resins having both a 36-carbon aliphatic skeleton derived from dimer amines (such as those manufactured by Inc.) and an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group; and so on.
[0047] The content of (C) maleimide resin in the resin composition is preferably 0.1% by mass or 0.3% by mass or more, more preferably 0.5% by mass or 0.8% by mass or more, even more preferably 1.0% by mass or 1.5% by mass or more, and particularly preferably 2.0% by mass or 2.5% by mass or more, when the nonvolatile components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 3.0% by mass or more, 3.5% by mass or more, 4.0% by mass or more, etc. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less or 15% by mass or less, and particularly preferably 12% by mass or less or 10% by mass or less. In one embodiment, it may be 8% by mass or less, 7% by mass or less, 6% by mass or less, 5.0% by mass or less, 4.5% by mass or less, etc. In one embodiment, the content of component (C) is preferably 1 to 15% by mass, when the non-volatile components in the resin composition are considered to be 100% by mass.
[0048] The content of (C) maleimide resin in the resin composition is preferably 0.5% by mass or more, more preferably 1.0% by mass or more or 2% by mass or more, even more preferably 3% by mass or more or 5% by mass or more, and particularly preferably 8% by mass or more or 10% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 11% by mass or more, 12% by mass or more, 13% by mass or more, 14% by mass or more, 15% by mass or more, etc. The upper limit is preferably 70% by mass or less or 65% by mass or less, more preferably 60% by mass or less or 55% by mass or less, even more preferably 50% by mass or less or 45% by mass or less, and particularly preferably 40% by mass or less, 35% by mass or less or 30% by mass or less. In one embodiment, it may be 28% by mass or less, 25% by mass or less, 22% by mass or less, 20% by mass or less, 18% by mass or less, 16% by mass or less, etc.
[0049] The total content of (A) epoxy resin, (B) active ester resin, and (C) maleimide resin in the resin composition is preferably 2% by mass or more or 5% by mass or more, more preferably 8% by mass or more or 10% by mass or more, even more preferably 12% by mass or more or 15% by mass or more, and particularly preferably 18% by mass or more, 20% by mass or more or 22% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass. The upper limit is preferably 70% by mass or less or 65% by mass or less, more preferably 60% by mass or less or 55% by mass or less, even more preferably 50% by mass or less, 45% by mass or less or 40% by mass or less, and particularly preferably 35% by mass or less, 30% by mass or less or 28% by mass or less. In one embodiment, it may be 26% by mass or less, 25% by mass or less, 24% by mass or less, etc.
[0050] The total content of (A) epoxy resin, (B) active ester resin, and (C) maleimide resin in the resin composition is preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more or 65% by mass or more, and particularly preferably 70% by mass or more or 75% by mass or more, when the total content of the resin components in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 80% by mass or more, 85% by mass or more, etc. The upper limit is preferably 99% by mass or less or 98% by mass or less, more preferably 97% by mass or less or 96% by mass or less, even more preferably 95% by mass or less, 94% by mass or less or 93% by mass or less, and particularly preferably 92% by mass or less, 91% by mass or less or 90% by mass or less.
[0051] <(C1) Maleimide resin having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less> In the resin composition of the present invention, component (C) comprises a maleimide resin having an aromatic ring (C1) and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less. By including component (C1), the dielectric loss tangent of the cured product can be effectively reduced. Component (C1) may be used alone or in combination of two or more types.
[0052] Component (C1) has an aromatic ring. The aromatic ring of component (C1) is as described in the [Explanation of Terms] section and may be either a monocyclic aromatic ring or a fused polycyclic aromatic ring. Furthermore, the aromatic ring may be either an aromatic carbocyclic ring or an aromatic heterocyclic ring.
[0053] From the viewpoint of significantly obtaining the effects of the present invention, the aromatic ring of component (C1) is preferably an aromatic carbocyclic ring. The aromatic carbocyclic ring may be either a monocyclic aromatic carbocyclic ring or a fused polycyclic aromatic carbocyclic ring, and its number of carbon atoms is preferably 6 to 14, more preferably 6 to 10. Therefore, the aromatic ring of component (C1) is preferably an aromatic carbocyclic ring having 6 to 14 carbon atoms, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring.
[0054] Component (C1) may or may not have a dimer amine skeleton. The dimer amine skeleton refers to the carbon skeleton obtained by removing the two terminal amino groups of a dimer amine. Dimer amines can be synthesized from dimer acids. In one embodiment, the number of carbon atoms in the dimer amine skeleton is preferably 36.
[0055] Dimer acids are known compounds obtained by dimerizing unsaturated fatty acids (preferably those with 11 to 22 carbon atoms, more preferably those with 14 to 20 carbon atoms, and especially preferably those with 18 carbon atoms), and their industrial production processes are largely standardized in the industry. Dimer acids that are readily available mainly consist of 36-carbon dimer acids obtained by dimerizing 18-carbon unsaturated fatty acids such as oleic acid and linoleic acid, which are particularly inexpensive and readily available. Dimer acids may also contain arbitrary amounts of monomeric acids, trimer acids, and other polymerized fatty acids, depending on the production method and degree of purification. Furthermore, although double bonds remain after the polymerization reaction of unsaturated fatty acids, in this specification, hydrogenated products obtained by further hydrogenation to reduce the degree of unsaturation are also included as dimer acids.
[0056] In component (C1), the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is 0.25 or less. In this invention, "number of aromatic rings" means the sum of the number of monocyclic aromatic rings and the number of condensed aromatic rings contained in the maleimide resin. That is, for the number of aromatic rings, a condensed aromatic ring is considered as one aromatic ring. For example, one benzene ring contained in the maleimide resin is counted as one aromatic ring, and one naphthalene ring is counted as one aromatic ring. In addition, the number of maleimide rings (maleimide groups) is not included in the number of aromatic rings. For example, in the case of the compound represented by the following formula (Y-1), the number of aromatic rings is 2, and in the case of the compound represented by the following formula (Y-2), the number of aromatic rings is 3.
[0057] [ka]
[0058] In one embodiment, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) is preferably 0.225 or less, more preferably 0.20 or less, even more preferably 0.175 or less, and particularly preferably 0.15 or less or 0.125 or less. Alternatively, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) may be 0. That is, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) can be 0 or more. If component (C1) does not have a dimeramine skeleton, the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is considered to be 0.
[0059] In one embodiment, if component (C1) does not have a dimeramine skeleton, it is preferable that the number of aromatic rings in one molecule of component (C1) is three or more. If component (C1) has a dimeramine skeleton, it is preferable that the number of aromatic rings in one molecule of component (C1) is five or more. That is, it is preferable that component (C1) is a maleimide resin having three or more aromatic rings in the molecule without a dimeramine skeleton, or a maleimide resin having a dimeramine skeleton and five or more aromatic rings in the molecule.
[0060] Specific examples of component (C1) include maleimide resins represented by the following formulas (C-1) to (C-5). Here, for the maleimide resin represented by the following formula (C-4), the number of dimer amine skeletons is m+1, the number of aromatic rings is 4m+8n, and the ratio of the number of elements (dimer amine / aromatic ring) is (m+1) / (4m+8n). Since n≧1, (m+1) / (4m+8n)≦(m+1) / (4m+8)≦(m+1) / (4m+4)=0.25, and the maleimide resin represented by the following formula (C-4) satisfies the requirements of component (C1).
[0061] [ka]
[0062] [ka]
[0063] [ka]
[0064] [ka] (In the above formula (C-4), each X is independently a divalent group represented by one of the following formulas (a') to (d'), where m≧0 and n≧1. In formulas (a') to (d'), * represents a bond to the nitrogen atom of the maleimide group, and m, n, p, and q are integers of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, respectively. Bonds shown by dashed lines represent carbon-carbon single bonds or carbon-carbon double bonds. However, if a bond shown by a dashed line is a carbon-carbon double bond, the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is one less than the number shown in formulas (a') to (d').)
[0065] [ka]
[0066] The maleimide resin represented by formula (C-4) above is obtained by carrying out an imidation reaction in which a tetracarboxylic acid diacid anhydride is reacted with either a dimer amine compound or a trimer triamine compound, as well as a full orange amine compound, and then maleimidizing the ends. The imidation reaction in the production of the maleimide resin represented by formula (C-4) can be carried out, for example, by referring to Japanese Patent No. 5534378.
[0067] (C1) component may be a commercially available product. Examples of commercially available (C1) component include "MIR-5000-60T" (maleimide resin represented by formula (C-3) above) manufactured by Nippon Kayaku Co., Ltd., "BMI-4200" (maleimide resin represented by formula (C-4) above) manufactured by Designer Molecules Inc., "SLK-2800" (maleimide resin represented by formula (C-4) above) manufactured by Shin-Etsu Chemical Co., Ltd., and "BMI-1000" (maleimide resin represented by formula (C-5) above) manufactured by Yamato Kasei Kogyo Co., Ltd.
[0068] The content of component (C1) in the resin composition is preferably 0.01% by mass or 0.05% by mass or more, more preferably 0.1% by mass or 0.3% by mass or more, even more preferably 0.5% by mass or 0.8% by mass or more, and particularly preferably 1.0% by mass or 1.2% by mass or more, when the nonvolatile components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.5% by mass or more, 1.8% by mass or more, 2.0% by mass or more, 2.5% by mass or more, 3.0% by mass or more, 3.5% by mass or more, 4.0% by mass or more, etc. The upper limit is preferably 20% by mass or less or 18% by mass or less, more preferably 15% by mass or less or 12% by mass or less, even more preferably 10% by mass or less or 8% by mass or less, and particularly preferably 6% by mass or less or 5% by mass or less.
[0069] The content of component (C1) in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more or 1.0% by mass or more, even more preferably 2% by mass or more or 3% by mass or more, and particularly preferably 4% by mass or more or 5% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 11% by mass or more, 12% by mass or more, 13% by mass or more, 14% by mass or more, 15% by mass or more, etc. The upper limit is preferably 50% by mass or less, 45% by mass or less or 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less or 25% by mass or less, and particularly preferably 20% by mass or less or 18% by mass or less.
[0070] The mass ratio of component (C1) to component (A) in the resin composition [(C1) component / (A) component] is preferably 0.001 or more, 0.003 or more, or 0.005 or more, more preferably 0.008 or more, 0.01 or more, or 0.03 or more, even more preferably 0.05 or more, 0.08 or more, or 0.10 or more, and particularly preferably 0.12 or more, 0.15 or more, or 0.18 or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.20 or more, 0.22 or more, 0.25 or more, 0.28 or more, 0.30 or more, 0.35 or more, 0.40 or more, 0.45 or more, 0.50 or more, 0.55 or more, 0.60 or more, etc. The upper limit is preferably 20 or less or 15 or less, more preferably 10 or less, 8 or less or 5 or less, even more preferably 4 or less, 3 or less or 2 or less, and particularly preferably 1.0 or less, 0.9 or less or 0.8 or less. In one embodiment, it may also be 0.7 or less, etc.
[0071] The mass ratio of component (C1) to component (B) in the resin composition [(C1) component / (B) component] is preferably 0.001 or more, or 0.003 or more, more preferably 0.005 or more, or 0.008 or more, even more preferably 0.01 or more, or 0.03 or more, and particularly preferably 0.05 or more, 0.08 or more, or 0.10 or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.12 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, etc. The upper limit is preferably 10 or less, or 8 or less, more preferably 5 or less, or 4 or less, even more preferably 3 or less, 2 or less, or 1.0 or less, and particularly preferably 0.8 or less, 0.6 or less, or 0.5 or less. In one embodiment, it may be 0.4 or less, etc.
[0072] <(C2) Maleimide resins that do not have aromatic rings, or have aromatic rings, but the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25> In the resin composition of the present invention, component (C) includes a maleimide resin that does not have an aromatic ring (C2), or has an aromatic ring, and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. By including component (C2), the dielectric loss tangent of the cured product can be effectively reduced, and the adhesion of the cured product to the copper substrate can be effectively improved. Component (C2) also contributes to obtaining a cured product that exhibits excellent adhesion to the copper substrate even when exposed to a high temperature and high humidity environment. Component (C2) may be used alone, or two or more types may be used in combination.
[0073] The (C2) component may or may not have an aromatic ring. If the (C2) component has an aromatic ring, the aromatic ring it possesses is as described in the [Explanation of Terms] section and may be either a monocyclic aromatic ring or a fused polycyclic aromatic ring. Furthermore, the aromatic ring may be either an aromatic carbocyclic ring or an aromatic heterocyclic ring.
[0074] When component (C2) has an aromatic ring, from the viewpoint of significantly obtaining the effects of the present invention, it is preferable that the aromatic ring of component (C2) is an aromatic carbon ring. The aromatic carbon ring may be either a monocyclic aromatic carbon ring or a fused polycyclic aromatic carbon ring, and its number of carbon atoms is preferably 6 to 14, more preferably 6 to 10. The aromatic ring of component (C2) is preferably an aromatic carbon ring having 6 to 14 carbon atoms, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring.
[0075] If component (C2) has aromatic rings, component (C2) has a dimeramine skeleton, and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. The method for counting the "number of aromatic rings" is as explained in the section "<Maleimide resin having aromatic rings (C1) and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less>". In one embodiment, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C2) (dimeramine / aromatic ring) is preferably greater than 0.275 or greater than 0.30, more preferably greater than 0.325 or greater than 0.35, even more preferably greater than 0.375, greater than 0.40 or greater than 0.425, and particularly preferably greater than 0.45, greater than 0.475 or greater than 0.50.
[0076] The dimer amine skeleton of component (C2) is the same as the dimer amine skeleton described in the section "<(C1) Maleimide resin having an aromatic ring and a ratio of the number of dimer amine skeletons to the number of aromatic rings (dimer amine / aromatic ring) of 0.25 or less>".
[0077] In one embodiment, the number of aromatic rings in one molecule of component (C2) is preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less. Furthermore, the number of aromatic rings in one molecule of component (C2) can be 0 or more. That is, component (C2) is preferably a maleimide resin having a dimer amine skeleton and containing 0 to 4 aromatic rings within the molecule.
[0078] In one embodiment, the (C2) component preferably includes a maleimide resin represented by the following formula (C2-3).
[0079] [ka] (In formula (C2-3), R independently represents a divalent hydrocarbon group containing a dimer amine skeleton. n represents a non-negative integer.)
[0080] In formula (C2-3), n represents an integer greater than or equal to 0. The upper limit of n is preferably 10 or less or 9 or less, more preferably 8 or less or 7 or less, even more preferably 6 or less or 5 or less, and particularly preferably 4 or less, 3 or less or 2 or less. The lower limit of n may be 1 or more. Also, n may be 0, 1 or 2.
[0081] In formula (C2-3), each R independently represents a divalent hydrocarbon group containing a dimer amine skeleton. R preferably has 36 carbon atoms.
[0082] In one embodiment, R is preferably a divalent group represented by the following formula (2) or (3).
[0083] [ka] (In equation (2), m1, n1, p1, and q1 are integers greater than or equal to 1. However, m1+n1 is between 6 and 17, and p1+q1 is between 8 and 19. Also, in equation (3), m2, n2, p2, and q2 are integers greater than or equal to 1. However, m2+n2 is between 6 and 17, and p2+q2 is between 8 and 19. Furthermore, in equations (2) and (3), dashed lines independently represent carbon-carbon single bonds or carbon-carbon double bonds, and * represents a bond to the nitrogen atom of the maleimide group.)
[0084] Among the groups represented by formula (2), the divalent group represented by formula (4) below is more preferred.
[0085] [ka] (In equation (4), the meaning of the symbols is the same as described above.)
[0086] Among these, a more preferred example of R is a divalent group represented by any of the following formulas (2-1) to (2-4) and formulas (3-1) to (3-2).
[0087] [ka] (In equations (2-1) to (2-4) and equations (3-1) to (3-2), the meaning of the symbols is the same as described above.)
[0088] Among these preferred examples, a more preferred example of R is a divalent group represented by any of the following formulas (2-5) to (2-8), (3-3), and (3-4). Of these, the group of formula (2-3) or the group of formula (3-3) is preferred, and the group of formula (2-3) is particularly preferred.
[0089] [ka] (In formulas (2-5) to (2-8), (3-3), and (3-4), * indicates a bond to the nitrogen atom of the maleimide group.)
[0090] Furthermore, a preferred specific example of a divalent group represented by formula (2-5) is the divalent group represented by formula (2-9) below. A preferred specific example of a divalent group represented by formula (2-7) is the divalent group represented by formula (2-10) below.
[0091] [ka] (In formulas (2-9) and (2-10), * represents a bond to the nitrogen atom of the maleimide group.)
[0092] In other words, in one embodiment, the (C2) component preferably includes a maleimide resin represented by the following formula (C2-1).
[0093] [ka] (In the formula, n represents a non-negative integer, and * represents a bond attached to the nitrogen atom of the maleimide group.)
[0094] Specific examples of component (C2) include maleimide resin represented by formula (C2-1) above, and maleimide resins represented by formulas (C2-4) to (C2-6) below. Here, for the maleimide resin represented by formula (C2-1) above, the number of dimeramine skeletons is n+1, the number of aromatic rings is 2n, and the ratio of the number of elements (dimeramine / aromatic ring) is (n+1) / 2n (=1 / 2 + 1 / 2n). Also, for the maleimide resin represented by formula (C2-4) below, the number of dimeramine skeletons is n+1, the number of aromatic rings is n, and the ratio of the number of elements (dimeramine / aromatic ring) is (n+1) / n (=1 + 1 / n). Furthermore, for the maleimide resin represented by the following formula (C2-5), the number of dimer amine skeletons is n+1, the number of aromatic rings is 4n, and the ratio of the number of elements (dimer amine / aromatic ring) is (n+1) / 4n (=1 / 4 + 1 / 4n).
[0095] [ka]
[0096] [ka]
[0097] [ka]
[0098] Component (C2) may be a commercially available product. Examples of commercially available components for component (C2) include "BMI-689" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-1) when n=0), "SLK-1500-T80" from Shin-Etsu Chemical Co., Ltd. (a maleimide resin represented by the above formula (C2-1) when n is an integer of 1 or more), "BMI-3000" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-4)), and "BMI-1700" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-5)).
[0099] The content of component (C2) in the resin composition is preferably 0.01% by mass or 0.03% by mass or more, more preferably 0.05% by mass or 0.08% by mass or more, and even more preferably 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, or 0.5% by mass or more, when the nonvolatile components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less or 15% by mass or less, even more preferably 12% by mass or less or 10% by mass or less, and particularly preferably 8% by mass or less or 6% by mass or less. In one embodiment, it may also be 5% by mass or less, 4% by mass or less, 3.0% by mass or less, 2.5% by mass or less, 2.0% by mass or less, 1.5% by mass or less, 1.0% by mass or less, 0.8% by mass or less, 0.6% by mass or less, etc.
[0100] The content of component (C2) in the resin composition is preferably 0.1% by mass or 0.3% by mass or more, more preferably 0.5% by mass or 0.8% by mass or more, even more preferably 1.0% by mass or more, and particularly preferably 1.2% by mass or more, 1.5% by mass or more, or 1.8% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 60% by mass or less or 55% by mass or less, more preferably 50% by mass or less or 45% by mass or less, even more preferably 40% by mass or less, 35% by mass or less, or 30% by mass or less, and particularly preferably 25% by mass or less, 20% by mass or less, or 18% by mass or less. In one embodiment, it may also be 15% by mass or less, 12% by mass or less, 10% by mass or less, 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3.0% by mass or less, 2.5% by mass or less, etc.
[0101] The mass ratio of component (C2) to component (A) in the resin composition [(C2) component / (A) component] is preferably 0.001 or more or 0.005 or more, more preferably 0.01 or more or 0.03 or more, and even more preferably 0.05 or more or 0.06 or more, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 20 or less or 15 or less, more preferably 10 or less or 8 or less, even more preferably 5 or less, 4 or less or 3 or less, and particularly preferably 2 or less, 1.0 or less or 0.8 or less. In one embodiment, it may also be 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, etc.
[0102] The mass ratio of component (C2) to component (B) in the resin composition [(C2) component / (B) component] is preferably 0.001 or higher, more preferably 0.005 or higher or 0.01 or higher, and even more preferably 0.03 or higher or 0.04 or higher, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 10 or less or 8 or less, more preferably 5 or less or 4 or less, even more preferably 3 or less, 2 or less or 1.0 or less, and particularly preferably 0.8 or less, 0.6 or less or 0.5 or less. In one embodiment, it may also be 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, 0.08 or less, 0.06 or less, 0.05 or less, etc.
[0103] The mass ratio of component (C1) to component (C2) in the resin composition [(C1) component / (C2) component] is preferably 0.01 or higher, more preferably 0.03 or higher, 0.05 or higher, or 0.08 or higher, even more preferably 0.1 or higher, and particularly preferably 0.3 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.5 or higher, 0.8 or higher, 1.0 or higher, 2 or higher, 3 or higher, 4 or higher, 5 or higher, 6 or higher, 7 or higher, 8 or higher, etc. The upper limit is preferably 100 or less or 80 or less, more preferably 50 or less or 30 or less, 20 or less or 15 or less, and even more preferably 10 or less. In one embodiment, the mass ratio [(C1) component / (C2) component] is preferably 0.1 to 100.
[0104] The mass ratio of the content of component (C2) to the total content of components (A) and (B) in the resin composition [(C2) component / ((A) component + (B) component)] is preferably 1.0 or less or 0.8 or less, more preferably 0.5 or less, 0.4 or less or 0.3 or less, even more preferably 0.2 or less, 0.1 or less or 0.08 or less, and particularly preferably 0.06 or less, 0.05 or less or 0.04 or less. In one embodiment, it may be 0.03 or less, etc. The lower limit is not particularly limited, but may be 0.001 or more, 0.005 or more, 0.01 or more, etc.
[0105] <(D) Phenolic resins (excluding those having a triazine skeleton)> The resin composition of the present invention contains (D) a phenolic resin (excluding those having a triazine skeleton). The inclusion of component (D) in the resin composition makes it possible to achieve both excellent dielectric properties (low dielectric loss tangent) and film stability in thin films. This is thought to be because the phenolic hydroxyl groups in component (D) trap radicals generated in the system by maleimide groups, etc., thereby suppressing radical reactions, and enabling the formation of a high-density structure even in thin films with a large thermal history where radicals are easily generated. Component (D) may be used alone or in combination of two or more types.
[0106] Component (D) preferably comprises atoms selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. In one embodiment, component (D) is more preferably a phenolic resin comprising carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. In another embodiment, component (D) is more preferably a phenolic resin comprising carbon atoms, hydrogen atoms, and oxygen atoms.
[0107] Component (D) has one or more phenolic hydroxyl groups (hydroxyl groups bonded to an aromatic ring) per molecule, preferably two or more. The aromatic ring of component (D) is preferably an aromatic carbon ring. The aromatic carbon ring may be either a monocyclic aromatic carbon ring or a fused polycyclic aromatic carbon ring, and its number of carbon atoms is preferably 6 to 14, more preferably 6 to 10. Therefore, the aromatic ring of component (D) is preferably an aromatic carbon ring with 6 to 14 carbon atoms, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring. Furthermore, from the viewpoint of heat resistance and water resistance, component (D) is preferably a novolac structure.
[0108] In one embodiment, component (D) preferably has an aromatic ring other than a phenol skeleton. Here, "aromatic ring other than a phenol skeleton" means "an aromatic ring to which a hydroxyl group is not attached." Furthermore, component (D) preferably does not have an alkyl group having 3 or more carbon atoms. That is, if component (D) has an alkyl group, the number of carbon atoms in the alkyl group of component (D) is preferably 2 or less, and more preferably 1 or less.
[0109] As mentioned above, component (D) does not have a triazine skeleton. By not having a triazine skeleton, the film degradation reaction catalyzed by the triazine skeleton can be suppressed, and the film stability can be improved. Furthermore, it is preferable that component (D) is a phenolic resin whose constituent atoms are selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. In other words, it is preferable that component (D) does not have nitrogen atoms as constituent atoms.
[0110] In one embodiment, component (D) is preferably a phenolic resin represented by the following formula (D-1).
[0111] [ka] (In formula (D-1), ring Ar 1 and ring Ar 2each independently represents an aromatic ring. L 1 each independently represents a divalent linking group. R 1 and R 2 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. Provided that at least one of R in formula (D-1) 1 and R 2 is a hydrogen atom. R 3 and R 4 each independently represent a substituent. m1 and m2 each independently represent an integer of 1 or more. m3 and m4 each independently represent an integer of 0 or more. n1 represents an integer of 0 or more.)
[0112] In formula (D-1), ring Ar 1 and ring Ar 2 each independently represent an aromatic ring. In formula (D-1), the n1 rings Ar 1 and the 1 ring Ar 2 may be the same as or different from each other. In one embodiment, in formula (D-1), the n1 rings Ar 1 and the 1 ring Ar 2 are preferably the same as each other. The aromatic ring in ring Ar 1 and ring Ar 2 is preferably an aromatic carbocycle. The number of carbon atoms in the aromatic ring in ring Ar 1 and ring Ar 2 is preferably 6 to 14, more preferably 6 to 10. Specific examples of ring Ar 1 and ring Ar 2 include a benzene ring, a naphthalene ring, an anthracene ring and the like, and a benzene ring or a naphthalene ring is preferred.
[0113] In formula (D-1), L 1 each independently represents a divalent linking group. In formula (D-1), the n1 L's 1 may be the same as or different from each other. In one embodiment, in formula (D-1), the n1 L's 1 are preferably the same as each other. L 1Preferably, the constituent atoms are atoms selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms; more preferably, the constituent atoms are atoms selected from the group consisting of carbon atoms, hydrogen atoms, and oxygen atoms; and even more preferably, the constituent atoms are carbon atoms and hydrogen atoms.
[0114] In one embodiment, L 1 Each of these is preferably a divalent group represented by the following formula (D-2).
[0115] [ka] (In formula (D-2), Ar L1 represents an arylene group. r represents 0 or 1. * represents a bond.
[0116] In formula (D-2), Ar L1 Ar represents an arylene group. An arylene group is a group obtained by removing two hydrogen atoms from the aromatic ring of an aromatic hydrocarbon compound. L1 The number of carbon atoms in the arylene group is preferably 6 to 14, and more preferably 6 to 12. L1 Specific examples include phenylene groups, biphenylene groups, naphthylene groups, etc., with phenylene groups or biphenylene groups being preferred. As mentioned above, component (D) preferably has an aromatic ring other than the phenol skeleton, and Ar L1 This corresponds to "aromatic rings other than the phenol skeleton."
[0117] In formula (D-2), r represents either 0 or 1. In one embodiment, r may be 0 or 1.
[0118] In formula (D-1), R 1 and R 2 Each of these independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. However, R in formula (D-1) 1 and R 2 At least one of them is a hydrogen atom. R in equation (D-1) 1 and R 2 If there are multiple instances, then there are multiple R1 and R 2 They may be the same or different from each other, but it is preferable that they be the same. 1 and R 2 The number of carbon atoms in the alkyl group is preferably 1 to 4, more preferably 1 to 3, even more preferably 1 or 2, and particularly preferably 1. 1 and R 2 Specific examples of alkyl groups in include methyl group, ethyl group, propyl group, isopropyl group, butyl group, sec-butyl group, isobutyl group, tert-butyl group, pentyl group, hexyl group, etc., with methyl group being preferred. In one embodiment, R 1 and R 2 Each of these is independently preferably a hydrogen atom or a methyl group, with a hydrogen atom being more preferable.
[0119] In formula (D-1), R 3 and R 4 Each of these independently represents a substituent. In formula (D-1), R 3 and R 4 If there are multiple instances, then there are multiple R 3 and R 4 They may be the same or different from each other, but it is preferable that they be the same. 3 and R 4 Preferably, each of these atoms is independently composed of an atom selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms. In one embodiment, R 3 and R 4 It is more preferable that each of them independently consists of a carbon atom, a hydrogen atom, an oxygen atom, and a phosphorus atom. In another embodiment, R 3 and R 4 Each of these atoms is more preferably composed of atoms selected from the group consisting of carbon atoms, hydrogen atoms, and oxygen atoms, and even more preferably composed of carbon atoms and hydrogen atoms.
[0120] R 3 and R 4 The number of carbon atoms is preferably 1 to 20, more preferably 1 to 14, and even more preferably 1 to 12.
[0121] R 3 and R 4 Examples of substituents in this compound include alkyl groups, alkenyl groups, and monovalent groups represented by the following formula (D-3). 3 and R 4 The number of carbon atoms in the alkyl group is preferably 1 to 6, more preferably 1 to 4, even more preferably 1 to 3, even more preferably 1 or 2, and particularly preferably 1. 3 and R 4 Specific examples of alkyl groups in this include methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, isobutyl, tert-butyl, pentyl, and hexyl groups, with methyl being preferred. 3 and R 4 The number of carbon atoms in the alkenyl group is preferably 2 to 6, more preferably 2 to 4, even more preferably 2 or 3, and particularly preferably 3. 3 and R 4 Specific examples of alkenyl groups in include vinyl group, allyl group, 1-propenyl group, butenyl group, sec-butenyl group, isobutenyl group, pentenyl group, hexenyl group, etc., with allyl group being preferred. In one embodiment, R 3 and R 4 Each of these is preferably a methyl group, an allyl group, or a monovalent group represented by formula (D-3), and more preferably a methyl group or a monovalent group represented by formula (D-3).
[0122] [ka]
[0123] In formula (D-1), m1 and m2 each independently represent an integer of 1 or more. In formula (D-1), the n1 m1s and the 1 m2 may be the same or different from each other. In one embodiment, it is preferable that the n1 m1s and the 1 m2 in formula (D-1) are the same from each other. Each of m1 and m2 is independently preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less. In one embodiment, each of m1 and m2 may independently be 1 or 2.
[0124] In formula (D-1), m3 and m4 each independently represent an integer of 0 or more. In formula (D-1), the n1 m3s and the 1 m4 may be the same or different from each other. In one embodiment, it is preferable that the n1 m3s and the 1 m4 in formula (D-1) are the same from each other. Each of m3 and m4 is independently preferably 4 or less, more preferably 3 or less, even more preferably 2 or less, and particularly preferably 1 or less. In one embodiment, each of m3 and m4 may independently be 0 or 1.
[0125] In equation (D-1), n1 represents an integer greater than or equal to 0. Preferably, n1 is an integer greater than or equal to 1.
[0126] As mentioned above, in equation (D-1), the ring Ar 1 , L 1 , R 1 , R 3 If there are multiple m1 and m3, they may be different from each other. That is, component (D) is the ring Ar 1 , L 1 , R 1 , R 3 The copolymer may be a copolymer of multiple repeating units in which at least one of m1 and m3 is different. Specific examples of such copolymers include phenolic resins represented by the following formula (D-1-6).
[0127] Specific examples of phenolic resins represented by formula (D-1) include phenolic resins represented by the following formulas (D-1-1) to (D-1-7).
[0128] [ka]
[0129] [ka]
[0130] [ka]
[0131] [ka]
[0132] [ka]
[0133] [ka]
[0134] [ka]
[0135] (D) Specific examples of components include, for example, "NHN", "CBN", "GPH", "GPH-65", and "GPH-103" from Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", "SN-375", "SN-395", and "SN-4110V" from Nippon Steel Chemical & Material Co., Ltd.; "TD-2090", "TD2131", "TD-2090-60M", "KA-1160", "KA-1163", and "KA-1165" from DIC Corporation; "HCA-HQ-HST" from Sanko Co., Ltd.; and "FATC809" from Gun-ei Chemical Industry Co., Ltd. These may be used individually or in combination of two or more types.
[0136] The content of component (D) in the resin composition is preferably 0.01% by mass or more, more preferably 0.03% by mass or more or 0.05% by mass or more, even more preferably 0.08% by mass or more or 0.1% by mass or more, and particularly preferably 0.2% by mass or more or 0.3% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.4% by mass or more, 0.5% by mass or more, 0.6% by mass or more, 0.7% by mass or more, 0.8% by mass or more, 0.9% by mass or more, 1.0% by mass or more, 1.1% by mass or more, 1.2% by mass or more, etc. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less or 15% by mass or less, even more preferably 10% by mass or less or 8% by mass or less, and particularly preferably 6% by mass or less or 5% by mass or less. In one embodiment, the amount may be 4% by mass or less, 3% by mass or less, 2.0% by mass or less, 1.5% by mass or less, etc. In one embodiment, the content of component (D) is preferably 0.1 to 10% by mass when the nonvolatile components in the resin composition are taken as 100% by mass.
[0137] The content of component (D) in the resin composition is preferably 0.05% by mass or 0.1% by mass or more, more preferably 0.3% by mass or 0.5% by mass or more, even more preferably 0.8% by mass or 1.0% by mass or more, and particularly preferably 1.2% by mass or 1.4% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.5% by mass or more, 2.0% by mass or more, 2.5% by mass or more, 3.0% by mass or more, 3.5% by mass or more, 4.0% by mass or more, etc. The upper limit is preferably 50% by mass or less or 45% by mass or less, more preferably 40% by mass or less or 35% by mass or less, even more preferably 30% by mass or less or 25% by mass or less, and particularly preferably 20% by mass or less or 18% by mass or less. In one embodiment, the amount may be 15% by mass or less, 12% by mass or less, 10% by mass or less, 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, etc.
[0138] The total content of components (A), (B), and (D) in the resin composition is preferably 3% by mass or more, more preferably 5% by mass or more or 10% by mass or more, even more preferably 12% by mass or more or 15% by mass or more, and particularly preferably 18% by mass or more or 19% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 20% by mass or more. The upper limit is preferably 65% by mass or less or 60% by mass or less, more preferably 55% by mass or less or 50% by mass or less, even more preferably 45% by mass or less, 40% by mass or less or 35% by mass or less, and particularly preferably 30% by mass or less, 25% by mass or less or 22% by mass or less.
[0139] The total content of components (A), (B), and (D) in the resin composition is preferably 25% by mass or 30% by mass or more, more preferably 35% by mass or 40% by mass or more, even more preferably 45% by mass or 50% by mass or more, and particularly preferably 55% by mass or 60% by mass or more, when the total content of the resin components in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 65% by mass or more, 70% by mass or more, 75% by mass or more, etc. The upper limit is preferably 97% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less, and particularly preferably 85% by mass or less. In one embodiment, it may be 85% by mass or less, etc.
[0140] The total content of components (A), (B), (C), and (D) in the resin composition is preferably 3% by mass or 5% by mass or more, more preferably 8% by mass or 10% by mass or more, even more preferably 12% by mass or 15% by mass or more, and particularly preferably 18% by mass or more, 20% by mass or more, or 22% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 24% by mass or more. The upper limit is preferably 75% by mass or less or 70% by mass or less, more preferably 65% by mass or less or 60% by mass or less, even more preferably 55% by mass or less, 50% by mass or less, or 45% by mass or less, and particularly preferably 40% by mass or less, 35% by mass or less, or 30% by mass or less. In one embodiment, it may be 28% by mass or less, 26% by mass or less, etc.
[0141] The total content of components (A), (B), (C), and (D) in the resin composition is preferably 60% by mass or more, more preferably 65% by mass or more or 70% by mass or more, even more preferably 75% by mass or more or 80% by mass or more, and particularly preferably 85% by mass or more or 90% by mass or more, when the total content of the resin components in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. There is no particular upper limit, but it may be 100% by mass or less, and may be 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, 98% by mass or less, 97% by mass or less, 96% by mass or less, 95% by mass or less, 94% by mass or less, etc.
[0142] The total content of components (B) and (D) in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or 3% by mass or more, even more preferably 5% by mass or 8% by mass or more, and particularly preferably 10% by mass or 12% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit is preferably 40% by mass or less, more preferably 35% by mass or less or 30% by mass or less, even more preferably 25% by mass or less or 20% by mass or less, and particularly preferably 18% by mass or less. In one embodiment, it may be 15% by mass or less, etc.
[0143] The total content of components (B) and (D) in the resin composition is preferably 10% by mass or more, more preferably 15% by mass or more or 20% by mass or more, even more preferably 25% by mass or more or 30% by mass or more, and particularly preferably 35% by mass or more or 40% by mass or more, when the total content of the resin components in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 45% by mass or more, 50% by mass or more, etc. The upper limit is preferably 90% by mass or less, more preferably 85% by mass or less or 80% by mass or less, even more preferably 75% by mass or less or 70% by mass or less, and particularly preferably 65% by mass or less or 60% by mass or less. In one embodiment, it may be 55% by mass or less, etc.
[0144] The mass ratio of component (D) to component (A) in the resin composition [(D) component / (A) component] is preferably 0.001 or more, 0.003 or more, 0.005 or more, or 0.008 or more, more preferably 0.01 or more, or 0.03 or more, and even more preferably 0.05 or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.08 or more, 0.10 or more, 0.12 or more, 0.15 or more, or 0.18 or more. The upper limit is preferably 20 or less or 15 or less, more preferably 10 or less or 8 or less, even more preferably 5 or less, 3 or less, or 2 or less, and particularly preferably 1.0 or less, 0.8 or less, 0.5 or less, or 0.4 or less. In one embodiment, it may be 0.3 or less, etc.
[0145] The mass ratio of component (D) to component (B) in the resin composition [(D) component / (B) component] is preferably 0.001 or higher, more preferably 0.003 or higher, even more preferably 0.005 or higher or 0.008 or higher, and particularly preferably 0.01 or higher or 0.03 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.05 or higher, 0.08 or higher, etc. The upper limit is preferably 20 or less or 15 or less, more preferably 10 or less, 8 or less or 5 or less, even more preferably 3 or less, 2 or less or 1.0 or less, and particularly preferably 0.8 or less or 0.5 or less. In one embodiment, it may be 0.4 or less, 0.3 or less, 0.2 or less, etc.
[0146] The ratio of the total number of moles of active groups (phenolic hydroxyl groups) of component (D) to the total number of moles of active groups (epoxy groups) of component (A) in the resin composition [total number of moles of active groups of component (D) / total number of moles of active groups of component (A)] is preferably 0.01 or higher, more preferably 0.03 or higher, and even more preferably 0.05 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.08 or higher, 0.10 or higher, 0.12 or higher, 0.15 or higher, 0.18 or higher, 0.20 or higher, etc. The upper limit is preferably 5 or lower, more preferably 3 or lower or 2 or lower, even more preferably 1 or lower or 0.8 or lower, and particularly preferably 0.6 or lower or 0.5 or lower. In one embodiment, it may be 0.4 or lower, 0.3 or lower, etc.
[0147] <(E) Inorganic filler> The resin composition of the present invention contains (E) an inorganic filler. By containing (E) an inorganic filler, the dielectric loss tangent of the cured product can be effectively reduced.
[0148] (E) Inorganic compounds can be used as the material for the inorganic filler. (E) Examples of inorganic fillers include silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Spherical silica is preferred as the shape of the silica. (E) The inorganic filler may be used alone or in combination of two or more types in any ratio.
[0149] (E) Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" from Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", "SC2300-SVJ", "SC2050-SXF", and "180nmSX-C1" from Admatex Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" from Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" from Tokuyama Corporation; "Cellspheres" and "MGH-005" from Taiheiyo Cement Corporation; and "LHP-208" from Ube Eximo Co., Ltd.
[0150] The average particle diameter of (E) inorganic filler is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 2 μm or less, still more preferably 1 μm or less, particularly preferably 0.7 μm or less or 0.6 μm or less, from the viewpoint of making the surface of the cured product (insulating layer) have low roughness and facilitating the formation of fine wiring. The lower limit of the average particle diameter of (E) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, particularly preferably 0.15 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.4 μm or more. The average particle diameter of (E) inorganic filler can be measured by a laser diffraction / scattering method based on Mie scattering theory. Specifically, it can be measured by creating a volume-based particle size distribution of the inorganic filler using a laser diffraction-scattering type particle size distribution analyzer, and taking the median diameter thereof as the average particle diameter. As the measurement sample, a sample obtained by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial, and dispersing the mixture with ultrasonic waves for 10 minutes can be used. The wavelengths of the light source used in the laser diffraction type particle size distribution analyzer can be blue and red, and the measurement can be performed by a flow cell method. Examples of the laser diffraction type particle size distribution analyzer include "LA-960" manufactured by HORIBA, Ltd.
[0151] The specific surface area of (E) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5 m 2 / g or more, further preferably 1 m 2 / g or more or 3 m 2 / g or more. The upper limit of the specific surface area of (E) inorganic filler is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70 m 2 / g or less, further preferably 50 m 2 / g or less, particularly preferably 40 m 2 / g or less, 30 m 2 / g or less, 20 m 2 / g or less or 10 m 2The value is less than / g. The specific surface area of the inorganic filler can be calculated using the BET method by adsorbing nitrogen gas onto the sample surface using a specific surface area measuring device (Macsorb HM-1210, manufactured by Mountec Co., Ltd.) and then using the BET multipoint method.
[0152] (E) The inorganic filler is preferably surface-treated with a surface treatment agent. Surface treatment can improve the moisture resistance and dispersibility of the (E) inorganic filler. Examples of surface treatment agents include vinyl silane coupling agents such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; and styryl silane coupling agents such as p-styryltrimethoxysilane. Methacryl silane coupling agents such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane; acrylic silane coupling agents such as 3-acryloxypropyltrimethoxysilane; N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-amino Amino-based silane coupling agents such as propyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-8-aminooctyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane; isocyanurate-based silane coupling agents such as tris(trimethoxysilylpropyl)isocyanurate; 3 -Ureidopropyltrialkoxysilane and other ureidopropyl silane coupling agents; mercaptopropyl silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate silane coupling agents such as 3-isocyanatetopropyltriethoxysilane; acid anhydride silane coupling agents such as 3-trimethoxysilylpropyl succinic anhydride; sulfide silane coupling agents such as bis(triethoxysilylpropyl)tetrasulfide;Examples include silane coupling agents such as methyltrimethoxysilane and phenyltrimethoxysilane, non-silane coupling alkoxysilane compounds, organosilazane compounds, and titanate coupling agents. Furthermore, the surface treatment agent may be used alone or in combination of two or more in any ratio. In one embodiment, (E) the inorganic filler is preferably surface-treated with an amino-based silane coupling agent, and more preferably with N-phenyl-3-aminopropyltrimethoxysilane.
[0153] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment by the surface treatment agent is preferably within a predetermined range. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 to 5 parts by mass of the surface treatment agent, more preferably with 0.2 to 3 parts by mass, and even more preferably with 0.3 to 2 parts by mass.
[0154] The degree of surface treatment by a surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler should be 0.02 mg / m². 2 The above is preferred, and 0.1 mg / m² 2 The above is more preferable, 0.2 mg / m² 2 The above is even more preferable. The upper limit is 1 mg / m². 2 The following is preferred: 0.8 mg / m² 2 The following is more preferable: 0.5 mg / m² 2 The following is even more preferable.
[0155] The carbon amount per unit surface area of (E) inorganic filler can be measured after subjecting the surface-treated inorganic filler to a washing treatment with a solvent (for example, methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler surface-treated with a surface treatment agent, followed by ultrasonic cleaning at 25°C for 5 minutes. After removing the supernatant liquid and drying the solid content, the carbon amount per unit surface area of the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, "EMIA-320V" manufactured by HORIBA, Ltd., or the like can be used.
[0156] In one embodiment, the resin composition of the present invention may contain a hollow inorganic filler as the (E) inorganic filler. The material of the hollow inorganic filler is as previously described for the inorganic filler, and among them, hollow silica, hollow alumina or hollow aluminosilicate is preferred, and hollow silica is more preferred.
[0157] The average porosity of the hollow inorganic filler is preferably 90% by volume or less, more preferably 85% by volume or less. The lower limit of the average porosity of the hollow inorganic filler is not particularly limited, but is, for example, more than 0% by volume, 1% by volume or more, preferably 5% by volume or more, more preferably 10% by volume or more, still more preferably 15% by volume or more, 20% by volume or more, 25% by volume or more or 30% by volume or more, and particularly preferably 35% by volume or more, 40% by volume or more or 45% by volume or more. The average porosity P (% by volume) of the inorganic filler is defined as the volume-based ratio of the total volume of pores present inside the particles to the total volume of the particles based on the outer surface of the particles (total pore volume / particle volume). The average porosity P (% by volume) of the inorganic filler is, for example, based on the measured value D of the actual density (apparent density) of the inorganic filler M (g / cm 3 ), and the theoretical value D of the material density of the material forming the inorganic filler T (g / cm 3 ), calculated by the following formula (I).
[0158]
Equation
[0159] The actual density (apparent density) of inorganic fillers can be measured, for example, using a true density analyzer. An example of a true density analyzer is the "ULTRAPYCNOMETER1000" manufactured by QUANTACHROME. Nitrogen is used as the measurement gas.
[0160] The resin composition of the present invention may contain only a solid inorganic filler, only a hollow inorganic filler, or a combination of a solid inorganic filler and a hollow inorganic filler as (E) the inorganic filler. In one embodiment, it is preferable that the resin composition of the present invention contains only a solid inorganic filler, or a combination of a solid inorganic filler and a hollow inorganic filler, as (E) the inorganic filler.
[0161] The content of (E) inorganic filler in the resin composition is preferably 30% by mass or 35% by mass or more, more preferably 40% by mass or 45% by mass or more, even more preferably 50% by mass or 55% by mass or more, and particularly preferably 60% by mass or 65% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 70% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less or 75% by mass or less.
[0162] <(F) Other hardening agents> The resin composition of the present invention may contain, as an optional component, a curing agent other than component (B) or component (D) ((F) other curing agent). (F) other curing agent may be used alone or in combination of two or more types.
[0163] (F) Other curing agents include, for example, carbodiimide-based curing agents, acid anhydride-based curing agents, amine-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, and thiol-based curing agents, with carbodiimide-based curing agents being preferred.
[0164] Examples of carbodiimide-based curing agents include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides like tetramethylene-bis(t-butylcarbodiimide) and cyclohexanebis(methylene-t-butylcarbodiimide); biscarbodiimides like aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). Examples of polycarbodiimides include poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(trylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and aromatic polycarbodiimides such as poly[methylenebis(methylphenylene)carbodiimide]; these may be used individually or in combination of two or more types.
[0165] Examples of commercially available carbodiimide-based curing agents include "Carbodilite V-02B," "Carbodilite V-03," "Carbodilite V-04K," "Carbodilite V-07," and "Carbodilite V-09" from Nisshinbo Chemical Co., Ltd., and "Stavaxol P," "Stavaxol P400," and "Hycazil 510" from Lanxess Corporation. These may be used individually or in combination of two or more types.
[0166] Examples of acid anhydride-based curing agents include curing agents having one or more acid anhydride groups in one molecule, and curing agents having two or more acid anhydride groups in one molecule are preferred. Specific examples of acid anhydride-based curing agents include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexen-1,2-dicarboxylic acid anhydride, trimellitic anhydride, pyromellitic anhydride, and bensophenone tetracarboxylic acid di Examples include anhydrides, biphenyltetracarboxylic acid dianhydride, naphthalenetetracarboxylic acid dianhydride, oxydiphthalic acid dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymer-type acid anhydrides such as styrene-maleic acid resin obtained by copolymerizing styrene and maleic acid. These may be used individually or in combination of two or more types.
[0167] Commercially available acid anhydride-based curing agents include "HNA-100," "MH-700," "MTA-15," "DDSA," and "OSA" from Shin Nippon Rika Co., Ltd.; "YH-306" and "YH-307" from Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" from Resonaq Corporation; and "EF-30," "EF-40," "EF-60," and "EF-80" from Clay Valley Corporation. These can be used individually or in combination of two or more types.
[0168] Examples of amine-based curing agents include curing agents having one or more, preferably two or more, amino groups in one molecule. The amino groups in the amine-based curing agent are preferably primary or secondary amino groups, with primary amino groups being more preferred. Examples of amine-based curing agents include aliphatic amines, polyetheramines, alicyclic amines, aromatic amines, and the like, among which aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary or secondary amine, with primary amines being more preferred.
[0169] Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl) Examples include propyl propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Amine-based curing agents may be commercially available, such as "SEIKACURE-S" from Seika Corporation, "KAYABOND C-200S," "KAYABOND C-100," "KAYAHARD AA," "KAYAHARD AB," and "KAYAHARD AS" from Nippon Kayaku Co., Ltd., "Epicure W" from Mitsubishi Chemical Corporation, and "DTDA" from Sumitomo Seika Co., Ltd. These may be used individually or in combination of two or more types.
[0170] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" from JFE Chemical Co., Ltd.; "HFB2006M" from Showa Polymer Co., Ltd.; and "Pd" and "Fa" from Shikoku Chemicals Co., Ltd. These may be used individually or in combination of two or more types.
[0171] Examples of cyanate ester curing agents include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl) thioether, and bis(4-cyanatephenyl) ether; polyfunctional cyanate resins derived from phenol novolacs and cresol novolacs; and prepolymers in which these cyanate resins are partially triazined. Specific examples of cyanate ester curing agents include "PT30" and "PT60" (both phenol novolac type polyfunctional cyanate ester resins) manufactured by arxada, "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazined and trimerized). These may be used individually or in combination of two or more types.
[0172] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl) isocyanurate. These may be used individually or in combination of two or more.
[0173] The content of (F) other curing agents in the resin composition is 0% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more, more preferably 0.03% by mass or more or 0.05% by mass or more, even more preferably 0.08% by mass or more or 0.1% by mass or more, and particularly preferably 0.3% by mass or more or 0.5% by mass or more. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less or 0.8% by mass or less.
[0174] The content of (F) other curing agents in the resin composition is 0% by mass or more, when the resin components in the resin composition are considered as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.05% by mass or more or 0.1% by mass or more, more preferably 0.3% by mass or more or 0.5% by mass or more, even more preferably 0.8% by mass or more or 1.0% by mass or more, and particularly preferably 1.5% by mass or more or 2.0% by mass or more. The upper limit is preferably 20% by mass or less or 15% by mass or less, more preferably 10% by mass or less or 8% by mass or less, even more preferably 6% by mass or less or 5% by mass or less, and particularly preferably 4% by mass or less or 3% by mass or less.
[0175] In the present invention, components (B), (D), and (F) are collectively referred to as the "curing agent." The ratio of the total number of moles of active groups (epoxy groups) of the curing agent to the total number of moles of active groups (epoxy groups) of component (A) in the resin composition [total number of moles of active groups of curing agent / total number of moles of active groups of component (A)] is preferably 0.1 or more or 0.3 or more, more preferably 0.5 or more or 0.8 or more, even more preferably 1.0 or more or 1.1 or more, and particularly preferably 1.2 or more or 1.3 or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.4 or more, 1.5 or more, 1.6 or more, etc. The upper limit is preferably 15 or less or 12 or less, more preferably 10 or less or 8 or less, even more preferably 5 or less or 4 or less, and particularly preferably 3.0 or less, 2.8 or less, or 2.5 or less. In one embodiment, it may be 2.2 or less, 2.0 or less, 1.8 or less, etc.
[0176] <(G)Organic filler> The resin composition of the present invention may contain (G) an organic filler as an optional component, and it is preferable that it contains (G) an organic filler. (G) an organic filler may be used alone or in combination of two or more types.
[0177] (G) The organic filler is present in particulate form in the resin composition. Examples of (G) organic fillers include rubber particles, polyamide fine particles, silicone particles, and core-shell type particles. In the present invention, from the viewpoint of significantly obtaining the desired effects of the present invention, (G) the organic filler preferably contains either rubber particles or core-shell type particles, more preferably rubber particles, and even more preferably core-shell type rubber particles.
[0178] Examples of rubber components included in rubber particles include olefin-based thermoplastic elastomers such as polybutadiene, polyisoprene, polychlorobutadiene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, and ethylene-propylene-butene terpolymer; and acrylic-based thermoplastic elastomers such as propyl poly(meth)acrylate, butyl poly(meth)acrylate, cyclohexyl poly(meth)acrylate, and octyl poly(meth)acrylate; and preferably acrylic-based thermoplastic elastomers. Rubber particles containing an acrylic-based thermoplastic elastomer as a rubber component are called "acrylic rubber particles." Core-shell type particles containing an acrylic-based thermoplastic elastomer as a rubber component are called "acrylic core-shell type particles." Core-shell type rubber particles containing an acrylic thermoplastic elastomer as a rubber component are called "acrylic core-shell type rubber particles." That is, (G) the organic filler preferably contains either acrylic rubber particles or acrylic core-shell type particles, more preferably acrylic rubber particles, and even more preferably acrylic core-shell type rubber particles. Furthermore, the rubber component may be mixed with silicone rubber such as polyorganosiloxane rubber. The rubber component contained in the rubber particles preferably has a glass transition temperature of 0°C or lower, more preferably -10°C or lower, even more preferably -20°C or lower, and particularly preferably -30°C or lower.
[0179] Commercially available rubber particles may be used, such as "EXL-2655" from Dow Chemical Japan, and "Stafyroid AC3401N" and "Stafyroid AC3816N" from Aica Kogyo Co., Ltd. "EXL-2655," "Stafyroid AC3401N," and "Stafyroid AC3816N" also fall under the category of core-shell type rubber particles.
[0180] Core-shell particles are particulate organic fillers having a core particle containing a rubber component as described above and one or more layers of shell covering it. In one embodiment, it is preferable that the core-shell particles are particulate organic fillers consisting of a core particle containing a rubber component as described above and one or more layers of shell covering it. Furthermore, it is preferable that the core-shell particles are core-shell graft copolymer particles having a core particle containing a rubber component as described above and a shell portion formed by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. It is even more preferable that the core-shell particles are core-shell graft copolymer particles consisting of a core particle containing a rubber component as described above and a shell portion formed by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. The term "core-shell type" as used here does not necessarily refer only to those in which the core particle and shell portion can be clearly distinguished, but also includes those in which the boundary between the core particle and shell portion is unclear, and the core particle does not have to be completely covered by the shell portion.
[0181] The rubber component is preferably contained in the core-shell type graft copolymer particles at a concentration of 40% by mass or more, more preferably at a concentration of 50% by mass or more, and even more preferably at a concentration of 60% by mass or more. The upper limit of the rubber component content in the core-shell type graft copolymer particles is not particularly limited, but from the viewpoint of sufficiently covering the core particles with the shell portion, it is preferably, for example, 95% by mass or less, or 90% by mass or less.
[0182] Examples of monomer components that form the shell portion of core-shell type graft copolymer particles include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimides; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; aromatic vinyl compounds such as styrene, 4-vinyltoluene, and α-methylstyrene; and (meth)acrylonitrile, with (meth)acrylic acid esters being preferred and methyl (meth)acrylate being more preferred.
[0183] Examples of commercially available core-shell type graft copolymer particles include "CHT" from Samsung SDI; "B602" from Techno UMG; "Paraloid EXL2602", "Paraloid EXL2603", "Paraloid EXL-2655", "Paraloid EXL2311", "Paraloid EXL2313", "Paraloid EXL2315", "Paraloid KM330", "Paraloid KM336P", and "Paraloid KCZ201" from Dow Chemical Japan; "Metabren C-223A", "Metabren E-901", "Metabren S-2001", "Metabren W-450A", and "Metabren SRK-200" from Mitsubishi Chemical Corporation; and "Kaneka M-511", "Kaneka M-600", "Kaneka M-400", "Kaneka M-580", and "Kaneka MR-01" from Kaneka Corporation. These may be used individually or in combination of two or more types.
[0184] The average particle size (average primary particle diameter) of the core-shell type graft copolymer particles is not particularly limited, but is preferably 20 nm or more, more preferably 50 nm or more, even more preferably 80 nm or more, and particularly preferably 100 nm or more. The upper limit is preferably 5,000 nm or less, more preferably 2,000 nm or less, even more preferably 1,000 nm or less, and particularly preferably 500 nm or less. The average particle size (average primary particle diameter) of the core-shell type graft copolymer particles can be measured using a zeta potential particle size distribution analyzer or the like.
[0185] The content of (G) organic filler in the resin composition is 0% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more or 0.03% by mass or more, more preferably 0.05% by mass or more or 0.08% by mass or more, even more preferably 0.1% by mass or more or 0.3% by mass or more, and particularly preferably 0.5% by mass or more or 0.6% by mass or more. The upper limit is preferably 15% by mass or less or 12% by mass or less, more preferably 10% by mass or less, 8% by mass or less or 6% by mass or less, even more preferably 5% by mass or less, 4% by mass or less or 3% by mass or less, and particularly preferably 2% by mass or less, 1.0% by mass or less or 0.8% by mass or less.
[0186] The content of (G) organic filler in the resin composition is 0% by mass or more, when the resin component in the resin composition is taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.05% by mass or more or 0.1% by mass or more, more preferably 0.3% by mass or more or 0.5% by mass or more, even more preferably 0.8% by mass or more or 1.0% by mass or more, and particularly preferably 1.2% by mass or more, 1.5% by mass or more, 1.8% by mass or more or 2.0% by mass or more. In one embodiment, it may be 2.2% by mass or more, 2.4% by mass or more, etc. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less, 15% by mass or less or 12% by mass or less, even more preferably 10% by mass or less, 8% by mass or less or 6% by mass or less, and particularly preferably 5% by mass or less, 4% by mass or less or 3% by mass or less.
[0187] When the resin composition of the present invention contains (G) an organic filler, the mass ratio of component (G) to component (E) in the resin composition [(G) component / (E) component] is preferably 1 × 10 from the viewpoint of significantly obtaining the effects of the present invention. -4 The above is futur3×10 -4 or more, or 5 x 10 -4 More preferably 8 × 10 -4 or more or 1 x 10 -3 In particular, 3 × 10 -3 The above 5 x 10 -3 or 8 x 10 -3 That is all. The upper limit is preferably 1 or less or 8 × 10 -1 The following is more preferable: 5 x 10 -1 The following or 3 x 10 -1 More preferably 1 × 10 -1 The following or 8 x 10 -2 The following is particularly preferred: 5 × 10 -2 The following or 3 x 10 -2 The following applies. In one embodiment, 1 × 10 -2 The following are possible options:
[0188] <(H)Thermoplastic resin> The resin composition of the present invention may further contain (H) thermoplastic resin as an optional component, and it is preferable that it contains (H) thermoplastic resin.
[0189] Examples of thermoplastic resins include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, and polyester resin. Among these, phenoxy resin is preferred from the viewpoint of significantly obtaining the effects of the present invention. The phenoxy resin described herein is a component other than epoxy resin. Furthermore, thermoplastic resins may be used individually or in combination of two or more types.
[0190] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group and an epoxy group.
[0191] Specific examples of the phenoxy resin include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both being phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Materials Co., Ltd.; and "YL6954BH30", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482" and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation; and the like.
[0192] Examples of the polyvinyl acetal resin include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred. Specific examples of the polyvinyl acetal resin include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.; and the like.
[0193] Examples of the polyolefin resin include ethylene-based copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin-based polymers such as polypropylene and ethylene-propylene block copolymer.
[0194] Specific examples of the polyimide resin include "Rikacoat SN20" and "Rikacoat PN20" manufactured by Nippon Rika Co., Ltd.
[0195] Specific examples of the polyamide-imide resin include "Vylomax HR11NN" and "Vylomax HR16NN" manufactured by Toyobo Co., Ltd. Further, specific examples of the polyamide-imide resin include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Resonac Corporation.
[0196] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0197] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers, LLC.
[0198] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.
[0199] From the viewpoint of remarkably obtaining the effects of the present invention, the weight average molecular weight (Mw) of the thermoplastic resin is preferably 8,000 or more, more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 70,000 or less, more preferably 60,000 or less, particularly preferably 50,000 or less.
[0200] The content of (H) thermoplastic resin in the resin composition is 0% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more or 0.03% by mass or more, more preferably 0.05% by mass or more or 0.08% by mass or more, even more preferably 0.1% by mass or more or 0.3% by mass or more, and particularly preferably 0.5% by mass or more or 0.8% by mass or more. The upper limit is preferably 20% by mass or less, 15% by mass or less or 12% by mass or less, more preferably 10% by mass or less, 8% by mass or less or 6% by mass or less, even more preferably 5% by mass or less, 4% by mass or less or 3% by mass or less, and particularly preferably 2.5% by mass or less, 2.0% by mass or less or 1.5% by mass or less.
[0201] The content of (H) thermoplastic resin in the resin composition is 0% by mass or more when the total resin components in the resin composition are considered as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.05% by mass or more or 0.1% by mass or more, more preferably 0.3% by mass or more or 0.5% by mass or more, even more preferably 0.8% by mass or more, 1.0% by mass or more or 1.5% by mass or more, and particularly preferably 2.0% by mass or more, 2.5% by mass or more or 3.0% by mass or more. The upper limit is preferably 40% by mass or less or 35% by mass or less, more preferably 30% by mass or less, 25% by mass or less or 20% by mass or less, even more preferably 15% by mass or less, 10% by mass or less or 8% by mass or less, and particularly preferably 6% by mass or less, 5% by mass or less or 4% by mass or less.
[0202] <(I) Curing accelerator> The resin composition of the present invention may contain (I) a curing accelerator as an optional component, and it is preferable that it contains (I) a curing accelerator. By including (I) a curing accelerator, it is possible to obtain a cured product that exhibits better dielectric properties (low dielectric loss tangent) while improving the curability of the resin composition. (I) A curing accelerator may be used alone or in combination of two or more types.
[0203] (I) Examples of curing accelerators include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, triazole-based curing accelerators, metal-based curing accelerators, amine-based curing accelerators, etc. (I) The curing accelerator may be used alone or in combination of two or more types. (I) The curing accelerator preferably contains an amine-based curing accelerator, a triazole-based curing accelerator, or an imidazole-based curing accelerator, and more preferably contains a triazole-based curing accelerator or an imidazole-based curing accelerator. In one embodiment, (I) the curing accelerator is even more preferably a triazole-based curing accelerator.
[0204] Examples of amine-based curing accelerators include trialkylamines such as triethylamine and tributylamine; pyridines such as 4-dimethylaminopyridine; and benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene. Pyridines are preferred, and 4-dimethylaminopyridine is more preferred. These may be used individually or in combination of two or more.
[0205] As amine-based curing accelerators, commercially available products may be used, such as "MY-25" manufactured by Ajinomoto Fine Techno Co., Ltd. and "DMAP" manufactured by Koei Chemical Industry Co., Ltd.
[0206] Examples of phosphorus-based curing accelerators include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium) pyromelitate, tetrabutylphosphonium hydrogen hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, and tetraphenylphosphonium bromide. Aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition products such as triphenylphosphine-p-benzoquinone addition products; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples include aromatic phosphines such as tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether. These may be used individually or in combination of two or more.
[0207] Examples of urea-based curing accelerators include aliphatic dimethylureas such as 1,1-dimethylurea, 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. Aromatic dimethylureas such as toluenebisdimethylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluenebisdimethylurea] are examples. These may be used individually or in combination of two or more.
[0208] Examples of guanidine-based curing accelerators include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]deca-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]deca-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. These may be used individually or in combination of two or more types.
[0209] Examples of imidazole-based curing accelerators include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, and 1-cyanoethyl-2-methylimidazole. , 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6 -[2'-Undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanurate adduct, 2-phenylimidazole isocyanurate adduct, 2-phenyl-4,5-dihydroxymethylimidazole Examples include imidazole compounds such as 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds with epoxy resins, with 1-benzyl-2-phenylimidazole being preferred. These may be used individually or in combination of two or more.
[0210] Examples of commercially available imidazole-based curing accelerators include "1B2PZ", "2P4MZ", "2M4MZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" from Shikoku Chemicals Corporation; and "P200-H50" from Mitsubishi Chemical Corporation. These may be used individually or in combination of two or more.
[0211] Examples of triazole-based curing accelerators include 1,2,3-benzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, carboxybenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazole-1-yl)methyl]imino]bisethanol, sodium salt of 1,2,3-benzotriazole, tolyltriazole, etc., with 1,2,3-benzotriazole being preferred. These may be used individually or in combination of two or more.
[0212] Examples of commercially available triazole-based curing accelerators include "BT-120," "BT-120SG," "BT-LX," "CBT-1," "CBT-SG," "TT-LX," "TT-LYK," "JCL-400," and "TT-130F" manufactured by Johoku Chemical Industry Co., Ltd. These may be used individually or in combination of two or more types.
[0213] Examples of metal-based curing accelerators include organometal complexes or organometal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometal complexes include organic cobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organic copper complexes such as copper(II) acetylacetonate, organic zinc complexes such as zinc(II) acetylacetonate, organic iron complexes such as iron(III) acetylacetonate, organic nickel complexes such as nickel(II) acetylacetonate, and organic manganese complexes such as manganese(II) acetylacetonate. Examples of organometal salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate. These may be used alone or in combination of two or more.
[0214] The content of the (I) curing accelerator in the resin composition is 0 mass% or more when the non-volatile components in the resin composition are taken as 100 mass%, and from the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.001 mass% or more or 0.005 mass% or more, more preferably 0.01 mass% or more or 0.03 mass% or more, still more preferably 0.05 mass% or more or 0.08 mass% or more, particularly preferably 0.10 mass% or more, 0.15 mass% or more or 0.18 mass% or more. The upper limit is preferably 10 mass% or less or 8 mass% or less, more preferably 5 mass% or less or 2 mass% or less, still more preferably 1 mass% or less, 0.8 mass% or less or 0.5 mass% or less, particularly preferably 0.4 mass% or less, 0.3 mass% or less or 0.25 mass% or less.
[0215] The content of (I) curing accelerator in the resin composition is 0% by mass or more when the resin components in the resin composition are considered as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more or 0.03% by mass or more, more preferably 0.05% by mass or more or 0.08% by mass or more, even more preferably 0.1% by mass or more or 0.3% by mass or more, and particularly preferably 0.5% by mass or more or 0.7% by mass or more. The upper limit is preferably 20% by mass or less or 15% by mass or less, more preferably 10% by mass or less or 8% by mass or less, even more preferably 5% by mass or less, 4% by mass or less or 3% by mass or less, and particularly preferably 2% by mass or less, 1.5% by mass or less or 1.0% by mass or less.
[0216] <(J) Organic Solvents> The resin composition of the present invention may contain (J) an organic solvent as an optional component. (J) may be used alone or in combination of two or more. In one embodiment, it is preferable to use two or more of (J) organic solvents in combination.
[0217] (J) Examples of organic solvents include organic solvents composed of atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, phosphorus atoms, sulfur atoms, halogen atoms, and hydrogen atoms. From the viewpoint of safety, (J) organic solvents are preferably organic solvents composed of atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms, and more preferably organic solvents composed of carbon atoms, oxygen atoms, and hydrogen atoms.
[0218] (J) Examples of organic solvents include glycol-based organic solvents, glycol ether-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, ester-based organic solvents, ether-based organic solvents, alcohol-based organic solvents, aliphatic hydrocarbon-based organic solvents, aromatic organic solvents, nitrogen-based organic solvents, sulfur-based organic solvents, halogen-based organic solvents, etc. Examples of nitrogen-based organic solvents include amide-based organic solvents, urea-based organic solvents, nitrile-based organic solvents, etc. From the viewpoint of safety, (J) organic solvents are preferably ester-based organic solvents, ketone-based organic solvents, glycol-based organic solvents, glycol ether-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, or aromatic organic solvents, more preferably ester-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, or aromatic organic solvents, even more preferably ketone-based organic solvents or aromatic organic solvents, and particularly preferably ketone-based organic solvents.
[0219] Examples of glycol-based organic solvents include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, and trimethylene glycol.
[0220] Examples of glycol ether-based organic solvents include cellosolves such as ethylene glycol monomethyl ether (also known as methyl cellosolve), ethylene glycol monoethyl ether (also known as cellosolve), ethylene glycol monopropyl ether (also known as propyl cellosolve), ethylene glycol monobutyl ether (also known as butyl cellosolve), ethylene glycol monoisobutyl ether (also known as isobutyl cellosolve), ethylene glycol mono-tert-butyl ether (also known as tert-butyl cellosolve), and ethylene glycol monohexyl ether; diethylene glycol monomethyl ether (also known as methyl carbitol), diethylene glycol monoethyl ether (also known as carbitol), and diethylene glycol monopropyl ether (also known as propyl Examples include carbitols such as carbitol and diethylene glycol monobutyl ether (DB) (also known as butyl carbitol); propylene glycol ethers such as propylene glycol monomethyl ether (PGM, also known as 1-methoxy-2-propanol), propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; and dipropylene glycol ethers such as dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, and dipropylene glycol monobutyl ether. Propylene glycol ethers are preferred, and propylene glycol monomethyl ether (1-methoxy-2-propanol) is more preferred.
[0221] Examples of glycol ether ester organic solvents include cellosolve esters such as ethylene glycol monomethyl ether acetate (also known as methyl cellosolve acetate), ethylene glycol monoethyl ether acetate (also known as cellosolve acetate), and ethylene glycol monobutyl ether acetate (also known as butyl cellosolve acetate); carbitol esters such as diethylene glycol monoethyl ether acetate (EDGAc) (also known as carbitol acetate) and diethylene glycol monobutyl ether acetate (also known as butyl carbitol acetate); propylene glycol ether esters such as propylene glycol monomethyl ether acetate (PGMEAc) and propylene glycol monoethyl ether acetate; and dipropylene glycol ether esters such as dipropylene glycol monomethyl ether acetate. Carbitol esters are preferred, and more preferred than diethylene glycol monoethyl ether acetate.
[0222] Examples of ketone-based organic solvents include aliphatic acyclic ketones such as acetone, methyl ethyl ketone (MEK), diethyl ketone, 2-pentanone, methyl isobutyl ketone, 2-hexanone, 2-heptanone (MAK), and diisobutyl ketone; aliphatic cyclic ketones such as cyclopentanone, cyclohexanone (Anone), and 2-methylcyclohexanone; and aromatic ketones such as acetophenone. Methyl ethyl ketone (MEK) or cyclohexanone are preferred. The lower limit of the number of carbon atoms in the ketone-based organic solvent is preferably 2 or more, more preferably 3 or more, and still more preferably 4 or more. The upper limit of the number of carbon atoms in the ketone-based organic solvent is preferably 10 or less, more preferably 8 or less, and still more preferably 6 or less.
[0223] Ester-based organic solvents are organic solvents having an ester structure that do not fall under the category of glycol ether ester-based organic solvents. Examples include fatty acid alkyl esters such as methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, sec-butyl acetate, tert-butyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, propyl propionate, and isopropyl propionate; alkyl hydroxy acid esters such as methyl lactate, ethyl lactate, and butyl lactate; alkyl keto acid esters such as methyl acetoacetate and ethyl acetoacetate; lactones such as γ-butyrolactone and α-acetyl-γ-butyrolactone; and aromatic esters such as methyl benzoate and ethyl benzoate. Lactones are preferred as ester-based organic solvents. Furthermore, the number of carbon atoms in the ester-based organic solvent is preferably 3 to 9.
[0224] Ether-based organic solvents are organic solvents having an ether structure that do not fall under glycol ether-based organic solvents or glycol ether ester-based organic solvents. Examples include aliphatic acyclic ethers such as dimethyl ether, diethyl ether, methyl ethyl ether, diisopropyl ether, dibutyl ether, methyl tert-butyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether; aliphatic cyclic ethers such as tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane; and aromatic ethers such as anisole and phenethole. The number of carbon atoms in ether-based organic solvents is preferably 2 to 9.
[0225] Alcohol-based organic solvents are organic solvents having an alcohol structure that do not fall under the category of glycol-based organic solvents or glycol ether-based organic solvents. Examples include aliphatic acyclic alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, n-pentyl alcohol, isopentyl alcohol, sec-pentyl alcohol, tert-pentyl alcohol, neopentyl alcohol, n-hexyl alcohol, n-heptyl alcohol, isoheptyl alcohol, n-octyl alcohol, and 2-ethylhexyl alcohol; aliphatic cyclic alcohols such as cyclohexanol; and aromatic alcohols such as benzyl alcohol and phenethyl alcohol.
[0226] Examples of aliphatic hydrocarbon organic solvents include n-pentane, n-hexane, 2-methylpentane (also known as isohexane), n-heptane, n-octane, cyclopentane, cyclohexane, methylcyclohexane, ethylcyclohexane, and decalin. The number of carbon atoms in the aliphatic hydrocarbon organic solvent is preferably 5 to 10.
[0227] Examples of aromatic organic solvents include benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, etc. 6-8 Aromatic hydrocarbons; C9 aromatic hydrocarbons such as 1,2,3-trimethylbenzene, 1,3,5-trimethylbenzene (also known as mesitylene), 1,2,4-trimethylbenzene, 4-ethyltoluene, 3-ethyltoluene, 2-ethyltoluene; C9 aromatic hydrocarbons such as 1,2-diethylbenzene, 1,3-diethylbenzene, 1,4-diethylbenzene, 3-ethyl-o-xylene, 4-ethyl-o-xylene, 2-ethyl-p-xylene, 1,2,3,5-tetramethylbenzene, tetralin, etc. 10 Aromatic hydrocarbons include aromatic heterocyclic compounds such as pyridine, furan, and thiophene, with toluene being preferred. The aromatic organic solvent preferably has 6 to 10 carbon atoms.
[0228] Examples of amide-based organic solvents include aliphatic acyclic amides such as N,N-dimethylacetamide and N,N-dimethylformamide; lactams such as N-methyl-2-pyrrolidone and N-cyclohexyl-2-pyrrolidone; and phosphate amides such as hexamethylphosphoramide. The number of carbon atoms in the amide-based organic solvent is preferably 2 to 10.
[0229] Examples of urea-based organic solvents include tetramethylurea and 1,3-dimethyl-2-imidazolinone.
[0230] Examples of nitrile-based organic solvents include acetonitrile, propionitrile, and benzonitrile. The number of carbon atoms in the nitrile-based organic solvent is preferably 2 to 10.
[0231] Examples of sulfur-based organic solvents include dimethyl sulfoxide.
[0232] Examples of halogenated organic solvents include chloroform, methylene chloride, carbon tetrachloride, and 1,2-dichloroethane. The halogenated organic solvent preferably has 1 to 10 carbon atoms.
[0233] Among these, (J) as organic solvents, γ-butyrolactone, methyl ethyl ketone (MEK), cyclopentanone, cyclohexanone, propylene glycol, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, or toluene are preferred; methyl ethyl ketone (MEK), cyclohexanone, diethylene glycol monoethyl ether acetate, γ-butyrolactone, propylene glycol monomethyl ether, or toluene are more preferred; methyl ethyl ketone (MEK), cyclohexanone, propylene glycol monomethyl ether, or toluene are even more preferred; and methyl ethyl ketone (MEK) or cyclohexanone are particularly preferred.
[0234] The content of (J) organic solvent in the resin composition is 0% by mass or more when the total components in the resin composition are considered as 100% by mass. From the viewpoint of obtaining a varnish with appropriate viscosity, it can be 1% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, etc. The upper limit can be 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, etc.
[0235] <(K) Other additives> The resin composition of the present invention may further contain (K) and other additives as optional components, to the extent that they do not hinder the objectives of the present invention. Examples of such additives include: radical polymerizable resins such as (meth)acrylic resins and styryl resins; radical polymerization initiators such as peroxide-based radical polymerization initiators and azo-based radical polymerization initiators; organometallic compounds such as organocopper compounds, organozinc compounds, and organocalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium dioxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentonite and montmorillonite; defoaming agents such as silicone-based defoaming agents, acrylic-based defoaming agents, fluorine-based defoaming agents, and vinyl resin-based defoaming agents; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; and tria Adhesion-enhancing agents such as zole-based adhesion enhancers, tetrazole-based adhesion enhancers, and triazine-based adhesion enhancers; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic acid anhydride-based stabilizers. The content of such additives may be determined according to the properties required of the resin composition. Furthermore, components (A) to (J) may have functions such as radical polymerizable resin, radical polymerization initiator, organometallic compound, colorant, polymerization inhibitor, leveling agent, thickener, defoamer, ultraviolet absorber, adhesion enhancer, adhesion imparter, antioxidant, fluorescent whitening agent, surfactant, flame retardant, dispersant, stabilizer, etc.In that case, the component in question will be considered as one of the components (A) through (J), rather than component (K).
[0236] <Method for producing resin compositions> The resin composition of the present invention can be prepared by appropriately mixing the necessary components from the above components (A) to (K), and, if necessary, by kneading or mixing with kneading means such as a three-roll mill, ball mill, bead mill, or sand mill, or stirring means such as a super mixer, planetary mixer, or high-speed rotary mixer.
[0237] <Physical properties and applications of resin compositions> In one embodiment, the cured product of the resin composition of the present invention exhibits a low dielectric loss tangent (Df) even at high temperatures. For example, as described in the section "Test Example 1: Measurement of Dielectric Loss Tangent" below, when measured at a measurement frequency of 10 GHz and a measurement temperature of 90°C, the dielectric loss tangent (Df) of the cured product of the resin composition of the present invention is preferably less than 0.0100 or less than 0.0080, more preferably less than 0.0060 or less than 0.0050, even more preferably less than 0.0045, less than 0.0040 or less than 0.0035, and particularly preferably less than 0.0032, less than 0.0030 or less than 0.0028.
[0238] In one embodiment, the cured product of the resin composition of the present invention exhibits a low dielectric loss tangent increase rate when the thickness of the insulating layer (cured product) is reduced. For example, as described in the section "Test Example 2: Measurement of Dielectric Loss Tangent Increase Rate" below, when the dielectric loss tangent (Df) of evaluation cured products with thicknesses of 25 μm and 40 μm is measured at a measurement frequency of 10 GHz and a measurement temperature of 90°C, the dielectric loss tangent increase rate, defined by the following formula, is preferably less than 5%.
[0239] Dielectric loss tangent increase rate (%) = ((Df of 25 μm evaluation cured material / Df of 40 μm evaluation cured material) - 1) × 100
[0240] In one embodiment, the resin composition of the present invention exhibits high film stability. For example, as described in the section <Test Example 3: Evaluation of Film Stability> below, the minimum melt viscosity (MV) of the resin composition layer immediately after manufacturing the resin sheet is high. 0h ), and the minimum melt viscosity (MV) of the resin composition layer after the resin sheet has been left standing at 23°C for 72 hours. 72h When measuring ), preferably 1.00 ≤ MV 72h / MV 0h The relationship <1.50 is satisfied.
[0241] In one embodiment, the cured product of the resin composition of the present invention exhibits high adhesion to the underlying copper. For example, the load used when measuring the peel strength, as described in the section "<Test Example 4: Evaluation Test of Adhesion to Underlying Copper>" below, is preferably 0.30 kgf / cm or more or 0.40 kgf / cm or more, more preferably 0.45 kgf / cm or more, even more preferably 0.50 kgf / cm or more, and particularly preferably 0.55 kgf / cm or more or 0.60 kgf / cm or more. The upper limit is not particularly limited, but it can be 10 kgf / cm or less, 1 kgf / cm or less, etc.
[0242] In one embodiment, the cured product of the resin composition of the present invention exhibits high adhesion to the underlying copper even when exposed to a high-temperature, high-humidity environment. For example, as described in the section "<Test Example 5: Evaluation Test of Adhesion to Underlying Copper After HAST>" below, the load used to measure the peel strength of a cured product exposed to an environment of 130°C and 85%RH for 100 hours is preferably 0.10 kgf / cm or more, 0.15 kgf / cm or more, or 0.20 kgf / cm or more, more preferably 0.25 kgf / cm or more, even more preferably 0.30 kgf / cm or more, even more preferably 0.35 kgf / cm or more, and particularly preferably 0.40 kgf / cm or more or 0.45 kgf / cm or more. The upper limit is not particularly limited, but it can be 10 kgf / cm or less, 1 kgf / cm or less, etc.
[0243] As described above, the resin composition of the present invention can produce a cured product that exhibits excellent dielectric properties (low dielectric loss tangent) even in thin films, while also having excellent adhesion to the underlying copper. Furthermore, the resin composition of the present invention has high film stability, which is advantageous in industrial processes. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for the insulating layer of a printed wiring board), and more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for the interlayer insulating layer of a printed wiring board). The resin composition of the present invention can also be suitably used when the printed wiring board is a circuit board with embedded components. The resin composition of the present invention can also be suitably used as a resin composition for forming an insulating layer of a redistribution substrate for a semiconductor package (resin composition for the insulating layer of a redistribution substrate). In this invention, printed wiring boards and redistribution substrates are collectively referred to as "circuit boards," and therefore the resin composition of the present invention can be suitably used for the insulating layer of a circuit board.
[0244] The resin composition of the present invention can be used in a wide range of applications where a resin composition is required, such as sheet-like laminated materials like resin sheets and prepregs, solder resists, underfill materials, die bonding materials, hole-filling resins, sealing resins, and component embedding resins.
[0245] [Sheet-like laminated materials (resin sheets, prepregs)] The resin composition of the present invention can be used as is, or it may be used in the form of a sheet-like laminated material containing the resin composition.
[0246] As sheet-like laminated materials, the following resin sheets and prepregs are preferred.
[0247] In one embodiment, the resin sheet comprises a support and a layer of a resin composition provided on the support (hereinafter simply referred to as the "resin composition layer"), wherein the resin composition layer is formed from the resin composition of the present invention.
[0248] The optimal thickness of the resin composition layer varies depending on the application and may be determined appropriately according to the application. For example, from the viewpoint of thinning printed circuit boards and semiconductor packages, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 1 μm or more, 5 μm or more, etc.
[0249] Examples of support materials include thermoplastic resin films, metal foils, and release paper, with thermoplastic resin films and metal foils being preferred. Therefore, in one preferred embodiment, the support material is a thermoplastic resin film or a metal foil.
[0250] When using a thermoplastic resin film as a support, examples of thermoplastic resins include polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); polycarbonate (PC); acrylic resins such as polymethyl methacrylate (PMMA); cyclic polyolefins; triacetylcellulose (TAC); polyether sulfide (PES); polyether ketones; and polyimides. Among these, polyester resins are preferred, polyethylene terephthalate or polyethylene naphthalate are more preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0251] When using a metal foil as a support, examples of metal foils include copper foil and aluminum foil, with copper foil being preferred. As for the copper foil, a foil containing a single metal of copper may be used, or a foil containing an alloy of copper with another metal (for example, tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used. In one embodiment, as the copper foil, a foil made of a single metal of copper may be used, or a foil made of an alloy of copper with another metal (for example, tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0252] The support may have a matte finish, corona treatment, or antistatic treatment applied to the surface that bonds with the resin composition layer. Alternatively, a support with a release layer may be used, which has a release layer on the surface that bonds with the resin composition layer. Examples of release agents used in the release layer of the support with a release layer include one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. Examples of commercially available release agents include "SK-1", "AL-5", and "AL-7" from Lintec Corporation. Furthermore, commercially available support with a release layer may also be used, for example, "Purex" from Toyobo Co., Ltd. and "Unipeel" from Unitika Corporation, which are PET films having a release layer mainly composed of alkyd resin-based release agents or polyolefin resin-based release agents.
[0253] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When using a support with a release layer, it is preferable that the overall thickness of the support with the release layer is within the above range.
[0254] When using metal foil as a support, a metal foil with a support substrate, which is formed by laminating a peelable support substrate onto a thin metal foil, may be used. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer provided on the support substrate, and a metal foil provided on the release layer. When using metal foil with a support substrate as a support, the resin composition layer is provided on the metal foil.
[0255] In a metal foil with a support substrate, the material of the support substrate is not particularly limited, but examples include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the support substrate, it may be electrolytic copper foil or rolled copper foil. Furthermore, the release layer is not particularly limited as long as it can be used to peel the metal foil from the support substrate, and examples include an alloy layer of elements selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, etc.
[0256] In a metal foil with a support substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.
[0257] In a metal foil with a support substrate, the thickness of the support substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, and more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.
[0258] In one embodiment, the resin sheet may further include any additional layer as needed. Such an additional layer may be, for example, a protective film provided on the side of the resin composition layer that is not bonded to the support (i.e., the side opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 75 μm, preferably 1 μm to 40 μm. By laminating the protective film, the adhesion of dust and other debris to the surface of the resin composition layer and scratches can be suppressed.
[0259] Resin sheets can be manufactured, for example, by applying a resin varnish prepared by directly using a liquid resin composition or by dissolving the resin composition in an organic solvent, coating it onto a support using a die coater or the like, and then drying it to form a resin composition layer.
[0260] Examples of organic solvents include those similar to those described as components of the resin composition. Organic solvents may be used individually or in combination of two or more.
[0261] Drying may be carried out by known methods such as heating or blowing hot air. The drying conditions are not particularly limited, but the resin composition layer should be dried so that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when using a resin composition or resin varnish containing 30% to 60% by mass of organic solvent, the resin composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.
[0262] Resin sheets can be stored by rolling them up. If the resin sheet has a protective film, it can be used after removing the protective film.
[0263] In one embodiment, the prepreg is formed by impregnating a sheet-like fibrous substrate with the resin composition of the present invention.
[0264] The sheet-like fibrous substrate used in the prepreg is not particularly limited, and commonly used prepreg substrates such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric can be used. From the viewpoint of thinning printed circuit boards and semiconductor packages, the thickness of the sheet-like fibrous substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fibrous substrate is not particularly limited, but is usually 10 μm or more.
[0265] Prepregs can be manufactured by known methods such as the hot melt method and the solvent method.
[0266] The thickness of the prepreg can be within the same range as the resin composition layer in the resin sheet described above.
[0267] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed circuit board (for the insulating layer of a printed circuit board), and more suitably used to form an interlayer insulating layer of a printed circuit board (for the interlayer insulating layer of a printed circuit board). The sheet-like laminated material of the present invention can also be suitably used to form an insulating layer of a redistribution substrate for a semiconductor package (for the insulating layer of a redistribution substrate). In other words, the sheet-like laminated material of the present invention can be suitably used as an insulating layer for a circuit board.
[0268] [Circuit board] An insulating layer of a circuit board can be formed using the resin composition of the present invention. The present invention also provides such a circuit board, that is, a circuit board including an insulating layer having a cured product of the resin composition of the present invention. In one embodiment, it is preferable that the circuit board of the present invention is a circuit board including an insulating layer made of a cured product of the resin composition of the present invention.
[0269] <Printed wiring board> In one embodiment, the circuit board of the present invention is a printed wiring board.
[0270] Printed circuit boards can be manufactured, for example, using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A process of laminating a resin sheet onto an inner layer substrate such that the resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., thermal curing) the resin composition layer to form an insulating layer.
[0271] The "internal layer substrate" used in process (I) is a material that serves as the substrate for a printed wiring board, and examples include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates, etc. The substrate may also have a conductive layer on one or both sides, and this conductive layer may be patterned. An internal layer substrate in which a conductive layer (circuit) is formed on one or both sides of the substrate is sometimes called an "internal layer circuit board." Furthermore, an intermediate product on which an insulating layer and / or a conductive layer is to be formed during the manufacturing of a printed wiring board is also included in the "internal layer substrate" as defined in this invention. If the printed wiring board is a circuit board with embedded components, an internal layer substrate with embedded components may be used.
[0272] The lamination of the inner layer substrate and the resin sheet can be performed, for example, by heating and pressing the resin sheet onto the inner layer substrate from the support side. Examples of the heating and pressing member used to heat and press the resin sheet onto the inner layer substrate (hereinafter also referred to as the "heat pressing member") include a heated metal plate (such as a SUS end plate) or a metal roll (such as a SUS roll). The heating and pressing member may be pressed directly onto the resin sheet, or it may be pressed via an elastic material such as heat-resistant rubber so that the resin sheet can adequately follow the surface irregularities of the inner layer substrate.
[0273] Lamination of the inner layer substrate and the resin sheet may be carried out by a vacuum lamination method. In the vacuum lamination method, the heat-pressure temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heat-pressure pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably in the range of 0.29 MPa to 1.47 MPa, and the heat-pressure time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination may preferably be carried out under reduced pressure conditions of 26.7 hPa or less.
[0274] Lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include vacuum pressure laminators manufactured by Meiki Seisakusho Co., Ltd., vacuum applicators manufactured by Nikko Materials Co., Ltd., and batch-type vacuum pressure laminators.
[0275] After lamination, the laminated resin sheets may be smoothed by pressing a heat-sealing member from the support side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing process can be the same as the heat-sealing conditions for lamination. The smoothing process can be performed using a commercially available laminator. Lamination and smoothing may be performed continuously using the commercially available vacuum laminator mentioned above.
[0276] The support may be removed between steps (I) and (II), or after step (II). If a metal foil is used as the support, the conductive layer may be formed using the metal foil without peeling off the support. If a metal foil with a support substrate is used as the support, the support substrate (and release layer) should be peeled off. Then, the conductive layer can be formed using the metal foil.
[0277] In step (II), the resin composition layer is cured (e.g., by thermal curing) to form an insulating layer having a cured resin composition. In one embodiment, it is preferable in step (II) to cure (e.g., by thermal curing) the resin composition layer to form an insulating layer consisting of a cured resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions commonly used when forming an insulating layer of a printed circuit board may be used.
[0278] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but in one embodiment, the curing temperature is preferably 140°C to 250°C, more preferably 150°C to 240°C, and even more preferably 180°C to 230°C. The curing time can be preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and even more preferably 15 minutes to 120 minutes.
[0279] Prior to thermal curing the resin composition layer, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermal curing the resin composition layer, it may be preheated at a temperature of 50°C to 140°C, preferably 60°C to 135°C, more preferably 70°C to 130°C for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0280] In manufacturing printed circuit boards, the following steps may be further performed: (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming the conductor layer. These steps (III) through (V) may be carried out according to various methods known to those skilled in the art that are used in the manufacture of printed circuit boards. If the support is removed after step (II), the removal of the support may be carried out between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). Furthermore, if necessary, the formation of the insulating layer and the conductor layer in steps (I) through (V) may be repeated to form a multilayer circuit board.
[0281] In other embodiments, the printed circuit board of the present invention can be manufactured using the prepreg described above. The manufacturing method is basically the same as when a resin sheet is used.
[0282] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as via holes and through holes in the insulating layer. Step (III) may be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined according to the design of the printed circuit board.
[0283] Step (IV) is a process for roughening the insulating layer. Typically, smear removal (desmear) is also performed in this step (IV). The procedure and conditions for the roughening process are not particularly limited, and known procedures and conditions commonly used when forming the insulating layer of a printed circuit board can be adopted. For example, the insulating layer can be roughened by performing swelling treatment with a swelling solution, roughening treatment with an oxidizing agent, and neutralization treatment with a neutralizing solution in this order.
[0284] The swelling solution used for the roughening treatment is not particularly limited, but examples include alkaline solutions and surfactant solutions, and is preferably an alkaline solution, with sodium hydroxide solution and potassium hydroxide solution being more preferred. Examples of commercially available swelling solutions include "Swelling Dip Securing P" and "Swelling Dip Securing SBU" manufactured by Atotec Japan. The swelling treatment with the swelling solution is not particularly limited, but can be carried out, for example, by immersing the insulating layer in a swelling solution at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling solution at 40°C to 80°C for 5 to 15 minutes.
[0285] The oxidizing agent used for the roughening treatment is not particularly limited, but examples include an alkaline permanganate solution obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide. The roughening treatment with an oxidizing agent such as an alkaline permanganate solution is preferably carried out by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 to 30 minutes. Furthermore, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Attec Japan.
[0286] Furthermore, an acidic aqueous solution is preferred as the neutralizing solution used in the roughening treatment. A commercially available example is "Reduction Solution Securigant P" manufactured by Attec Japan.
[0287] The neutralization treatment can be carried out by immersing the treated surface, which has been roughened with an oxidizing agent, in a neutralization solution at 30°C to 80°C for 5 to 30 minutes. From the standpoint of workability, it is preferable to immerse the object, which has been roughened with an oxidizing agent, in a neutralization solution at 40°C to 70°C for 5 to 20 minutes.
[0288] Step (V) is a step of forming a conductive layer, in which a conductive layer is formed on an insulating layer. The conductive material used for the conductive layer is not particularly limited. In a preferred embodiment, the conductive layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductive layer may be a single-metal layer or an alloy layer, and examples of alloy layers include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). In particular, from the viewpoint of versatility in conductor layer formation, cost, and ease of patterning, single metal layers of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or alloy layers of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy are preferred, single metal layers of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or alloy layers of nickel-chromium alloy are more preferred, and single metal layers of copper are even more preferred.
[0289] The conductive layer may be a single layer or a multilayer structure in which two or more single-metal layers or alloy layers containing different types of metals or alloys are laminated. In one embodiment, the conductive layer may be a single layer or a multilayer structure in which two or more single-metal layers or alloy layers made of different types of metals or alloys are laminated. When the conductive layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single-metal layer of chromium, zinc, or titanium, or an alloy layer of nickel-chromium alloy.
[0290] The thickness of the conductor layer depends on the desired printed circuit board design, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0291] In one embodiment, the conductor layer may be formed by plating. From the viewpoint of easily forming fine wiring, it is preferable to form it by a semi-additive method. An example of forming the conductor layer by a semi-additive method is shown below.
[0292] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer, exposing a portion of the plating seed layer corresponding to the desired wiring pattern. After forming a metal layer on the exposed plating seed layer by electroplating, the mask pattern is removed. Subsequently, the unnecessary plating seed layer can be removed by etching or other means to form a conductor layer having the desired wiring pattern.
[0293] In other embodiments, the conductor layer may be formed using metal foil. When forming the conductor layer using metal foil, step (V) is preferably performed between steps (I) and (II). For example, after step (I), the support is removed and the metal foil is laminated onto the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is performed to form an insulating layer. Subsequently, the metal foil on the insulating layer can be used to form a conductor layer having a desired wiring pattern by conventional known techniques such as the modified semi-additive method.
[0294] Metal foils can be manufactured by known methods such as electrolysis and rolling. Examples of commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Nippon Oil & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0295] Alternatively, as mentioned above, if a metal foil or a metal foil with a support substrate is used as the support for the resin sheet, the conductive layer may be formed using the metal foil.
[0296] <Semiconductor package redistribution substrate> In one embodiment, the circuit board of the present invention is a redistribution substrate (redistribution layer) for a semiconductor package. The following description will be based on the manufacturing method of the semiconductor package.
[0297] The semiconductor package includes an insulating layer having a cured product of the resin composition of the present invention as an insulating layer of the redistribution substrate. In one embodiment, it is preferable that the semiconductor package includes an insulating layer made of a cured product of the resin composition of the present invention as an insulating layer of the redistribution substrate. The semiconductor package may also include a sealing layer having a cured product of the resin composition of the present invention. In one embodiment, the semiconductor package may include a sealing layer made of a cured product of the resin composition of the present invention.
[0298] A semiconductor package can be manufactured, for example, using the resin composition and resin sheet of the present invention by a method including the following steps (1) to (6). The resin composition and resin sheet of the present invention may be used to form the redistribution layer (insulating layer for forming a redistribution substrate) in step (5) or the sealing layer in step (3). An example of forming a redistribution layer and a sealing layer using the resin composition and resin sheet is shown below, but the techniques for forming redistribution layers and sealing layers of semiconductor packages are well known, and those skilled in the art can manufacture semiconductor packages using the resin composition and resin sheet of the present invention in accordance with known techniques. (1) A step of laminating a temporary fixing film onto the substrate, (2) A step of temporarily fixing the semiconductor chip onto a temporary fixing film, (3) A step of forming a sealing layer on a semiconductor chip, (4) Steps to peel off the substrate and temporary fixing film from the semiconductor chip, (5) A step of forming a rewiring layer as an insulating layer on the surface from which the substrate and temporary fixing film of the semiconductor chip have been peeled off, and (6) Step of forming a redistribution layer as a conductor layer on the redistribution formation layer.
[0299] <<Process (1)>> The material used for the substrate is not particularly limited. Examples of substrates include semiconductor wafers such as silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates made by impregnating glass fibers with epoxy resin and heat-curing treatment (e.g., FR-4 substrates); and bismaleimidotriazine resin (BT resin) substrates. In one embodiment, the bismaleimidotriazine resin (BT resin) substrate is a substrate made of bismaleimidotriazine resin (BT resin).
[0300] The temporary fixing film is not limited in material as long as it can be peeled off from the semiconductor chip in step (4) and temporarily fix the semiconductor chip. Commercially available temporary fixing films can be used. Examples of commercially available products include Riva Alpha manufactured by Nitto Denko Corporation.
[0301] <<Process (2)>> Temporary fixing of semiconductor chips can be performed using known devices such as flip-chip bonders and die bonders. The layout and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixing film, the number of semiconductor packages to be produced, etc. For example, they can be temporarily fixed in a matrix arrangement with multiple rows and multiple columns.
[0302] <<Process (3)>> The resin composition layer of the resin sheet of the present invention is laminated onto a semiconductor chip, or the resin composition of the present invention is applied onto a semiconductor chip and cured (e.g., by heat curing) to form a sealing layer.
[0303] For example, lamination of a semiconductor chip and a resin sheet can be performed by removing the protective film from the resin sheet and then heating and pressing the resin sheet onto the semiconductor chip from the support side. Examples of the heating and pressing member used to heat and press the resin sheet onto the semiconductor chip (hereinafter also referred to as the "heating and pressing member") include a heated metal plate (such as a SUS end plate) or a metal roll (such as a SUS roll). It is preferable to press the resin sheet via an elastic material such as heat-resistant rubber, rather than directly pressing the heating and pressing member onto the resin sheet, so that the resin sheet can adequately follow the surface irregularities of the semiconductor chip. Lamination of the semiconductor chip and the resin sheet may also be carried out by a vacuum lamination method, and the lamination conditions are the same as those described in relation to the manufacturing method of printed circuit boards, and the preferred range is also the same.
[0304] After lamination, the resin composition is heat-cured to form a sealing layer. The heat-curing conditions are the same as those described in relation to the manufacturing method of printed circuit boards.
[0305] The resin sheet support may be peeled off after the resin sheet has been laminated onto the semiconductor chip and heat-cured, or the support may be peeled off before the resin sheet has been laminated onto the semiconductor chip.
[0306] When applying the resin composition of the present invention to form a sealing layer, the application conditions are the same as those for forming the resin composition layer described in relation to the resin sheet of the present invention, and the preferred ranges are also the same.
[0307] <<Process (4)>> The method for peeling off the substrate and the temporary fixing film can be appropriately changed depending on the material of the temporary fixing film, etc. Examples include a method of peeling off the temporary fixing film by heating and foaming (or expanding) it, and a method of peeling off the temporary fixing film by irradiating it with ultraviolet light from the substrate side to reduce the adhesive strength of the temporary fixing film.
[0308] In the method of peeling off a temporary fixing film by heating and foaming (or expanding) it, the heating conditions are usually 100-250°C for 1-90 seconds or 5-15 minutes. In the method of peeling off a temporary fixing film by irradiating it with ultraviolet light from the substrate side to reduce its adhesive strength, the amount of ultraviolet light irradiated is usually 10 mJ / cm². 2 ~1000 mJ / cm 2 That is the case.
[0309] <<Process (5)>> The present invention provides a resin composition and resin sheet used to form a rewiring layer (an insulating layer for a rewiring substrate).
[0310] After forming the redistribution layer, via holes may be formed in the redistribution layer to interlayer connect the semiconductor chip with the conductor layer described later. The via holes may be formed by known methods depending on the material of the redistribution layer.
[0311] <<Process (6)>> The formation of the conductor layer on the rewiring layer may be carried out in the same manner as in step (V) described in relation to the manufacturing method of a printed circuit board. Alternatively, steps (5) and (6) may be repeated to alternately stack the conductor layer (rewiring layer) and the rewiring layer (insulating layer) (build-up).
[0312] In manufacturing a semiconductor package, the following steps may be further performed: (7) forming a solder resist layer on a conductor layer (redistribution layer), (8) forming bumps, and (9) dicing multiple semiconductor packages into individual semiconductor packages to form individual pieces. These steps may be carried out in accordance with various methods known to those skilled in the art that are used in the manufacture of semiconductor packages.
[0313] The resin composition and resin sheet of the present invention, which can produce a cured product exhibiting low dielectric loss tangent, excellent smear removal properties, and high heat resistance (glass transition temperature), can be used to form a redistribution layer (insulating layer) to realize a semiconductor package with extremely low transmission loss, regardless of whether it is a fan-in or fan-out type package, without concerns about cracks or circuit distortion. In one embodiment, the semiconductor package of the present invention is a fan-out type package. The resin composition and resin sheet of the present invention can be applied to fan-out type panel-level packages (FOPLPs) and fan-out type wafer-level packages (FOWLPs). In one embodiment, the semiconductor package of the present invention is a fan-out type panel-level package (FOPLP) or a fan-out type wafer-level package (FOWLP).
[0314] [Semiconductor device] The semiconductor device of the present invention includes an insulating layer having a cured product of the resin composition of the present invention. In one embodiment, it is preferable that the semiconductor device of the present invention includes an insulating layer made of a cured product of the resin composition of the present invention. That is, the semiconductor device of the present invention includes a circuit board of the present invention. The semiconductor device of the present invention can be manufactured using the circuit board of the present invention.
[0315] Examples of semiconductor devices include various types of semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, and televisions) and vehicles (e.g., motorcycles, automobiles, trains, ships, and aircraft). [Examples]
[0316] The present invention will be described in detail below with reference to examples. The present invention is not limited to these examples. In the following, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "% by mass," respectively.
[0317] <Synthesis Example 1: Synthesis of Active Ester Resin (B-1)> In a flask equipped with a thermometer, dropping funnel, condenser, fractionation column, and stirrer, 320 g (2.0 mol) of 2,7-dihydroxynaphthalene, 184 g (1.7 mol) of benzyl alcohol, and 5.0 g of p-toluenesulfonic acid monohydrate were charged and stirred at room temperature while blowing in nitrogen. Then, the temperature was raised to 150°C and the mixture was stirred for 4 hours while distilling off the water produced. After the reaction was complete, 900 g of methyl isobutyl ketone and 5.4 g of 20% sodium hydroxide aqueous solution were added to neutralize the mixture. The aqueous layer was then removed by liquid-liquid extraction, and the organic layer was washed three times with 280 g of water. Methyl isobutyl ketone was removed from the resulting organic layer under reduced pressure to obtain 460 g of benzyl-modified naphthalene compound (B-1'). The obtained benzyl-modified naphthalene compound (B-1') was a black solid with a hydroxyl group equivalent of 180 g / eq.
[0318] In a flask equipped with a thermometer, dropping funnel, condenser, fractionation column, and stirrer, 203.0 g of isophthalic acid chloride (2.0 moles of acid chloride groups) and 1400 g of toluene were charged, and the system was dissolved under reduced pressure and nitrogen purging. Next, 113.9 g (0.67 moles) of orthophenylphenol and 240 g of benzyl-modified naphthalene compound (B-1') (1.33 moles of phenolic hydroxyl groups) were charged, and the system was dissolved under reduced pressure and nitrogen purging. Subsequently, 0.70 g of tetrabutylammonium bromide was dissolved, and while purging with nitrogen gas, the system temperature was controlled to below 60°C, and 400 g of 20% sodium hydroxide aqueous solution was added dropwise over 3 hours. Stirring was then continued under these conditions for 1.0 hour. After the reaction was complete, the mixture was allowed to stand and separated, and the aqueous layer was removed. Furthermore, water was added to the toluene layer in which the product was dissolved, and the mixture was stirred for 15 minutes. The aqueous layer was then removed by standing liquid-liquid extraction. This procedure was repeated until the pH of the aqueous layer reached 7. Subsequently, water was removed by decanting to obtain activated ester resin (B-1) in a toluene solution with 65% by mass of nonvolatile components. The active ester equivalent of the obtained activated ester resin (B-1) was 238 g / eq.
[0319] [ka]
[0320] <Synthesis Example 2: Synthesis of Maleimide Resin (C-1)> According to Synthesis Example 1 in the Japan Institute of Invention and Innovation Published Technical Report No. 2020-500211, a MEK solution (62% by mass of non-volatile components) of maleimide resin (C-1) represented by the following formula (C-1) was prepared. The Mw / Mn of this maleimide resin (C-1) was 1.81, and t'' in formula (C-1) was 1.47 (mainly 1, 2, or 3).
[0321] [ka]
[0322] <Synthesis Example 3: Synthesis of Maleimide Resin (C-2)> (I) Synthesis of intermediate amine compound (c) In a flask equipped with a thermometer, condenser, Dean-Stark trap, and stirrer, 400 g (3.3 mol) of 2-ethylaniline, 127 g of compound (b) having a benzyl ether skeleton (Nikanol L, manufactured by Fudo Co., Ltd.), 193 g of toluene, and 53 g of activated clay were charged. The mixture was heated to 120°C while stirring and held for 30 minutes. Then, the temperature was raised to 150°C and held for 3 hours. After holding, the temperature was raised to 200°C over 30 minutes and held for 10 hours. After holding, the mixture was diluted with 193 g of toluene, and the activated clay was filtered off. From the filtrate, the solvent and excess 2-ethylaniline were removed by heating and reduced pressure to obtain the intermediate amine compound (c) (amine equivalent 209 g / eq.).
[0323] (II) Maleimidization A 2L flask equipped with a thermometer, condenser, Dean-Stark trap, and stirrer was charged with 73.2g (126 mol, 1.3 equivalents) of maleic anhydride and 461g of toluene, and stirred at room temperature. Next, a mixed solution of intermediate amine compound (c) 209g (1 equivalent) and N,N-dimethylformamide (DMF) 57.7g was added dropwise over 1 hour, and the reaction was allowed to proceed for 2 hours. 9.72g of p-toluenesulfonic acid monohydrate was added to the reaction solution, and the solution was heated to 115°C. The azeotropic water and toluene were cooled and separated under reflux, and only toluene was returned to the system for dehydration for 5 hours. After air cooling to room temperature, the brown solution obtained by concentration under reduced pressure was dissolved in 600g of ethyl acetate and washed three times with 200g of deionized water and three times with 150g of 2% by mass sodium bicarbonate aqueous solution. After adding sodium sulfate and drying, the product was concentrated under reduced pressure and vacuum-dried at 80°C for 4 hours to obtain maleimide resin (C-2). Maleimide resin (C-2) mainly contained a maleimide compound represented by the following formula (C-2). In formula (C-2), n represents an integer of 1 or more, and n 1 Each of these independently represents the number of repeating units, and Et represents the ethyl group.
[0324] [ka]
[0325] <Examples 1-32 and Comparative Examples 1-7> (1) Manufacturing of resin composition Each component was weighed and mixed according to the formulations shown in Tables 1, 3, 5, and 7, and uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (varnish). Tables 2, 4, 6, and 8 show the evaluation results of the test examples described below.
[0326] [Table 1]
[0327] [Table 2]
[0328] [Table 3]
[0329] [Table 4]
[0330] [Table 5]
[0331] [Table 6]
[0332] [Table 7]
[0333] [Table 8]
[0334] The details of each component listed in the table are as follows. (A) Epoxy resin • NC-3000L: Epoxy equivalent 271g / eq., manufactured by Nippon Kayaku Co., Ltd., biphenyl-type epoxy resin HP-4032SS: Epoxy equivalent 144g / eq., manufactured by DIC Corporation, naphthalene-type epoxy resin
[0335] (B) Active ester resin • HPC-8000L-65MT: Active ester equivalent 220 g / eq., manufactured by DIC Corporation, active ester resin containing a dicyclopentadiene-type diphenol structure, mixed solution of MEK and toluene with 65% non-volatile components. • Activated ester resin (B-1): Activated ester resin (B-1) obtained in Synthesis Example 1, 238 g / eq. of activated ester equivalent, toluene solution with 62% non-volatile components. • Activated ester resin (B-2): Activated ester resin (B-2) represented by the following formula (mainly composed of compounds where n is an integer from 0 to 6), 250 g / eq. of activated ester equivalent, toluene solution with 60% non-volatile components.
[0336] [ka]
[0337] • Activated ester resin (B-3): Activated ester resin (B-3) represented by the following formula (mainly composed of compounds where n is an integer from 0 to 6), 249 g / eq. of activated ester equivalent, toluene solution with 65% non-volatile components.
[0338] [ka]
[0339] (C1) Maleimide resin having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less. • Maleimide resin (C-1): Maleimide resin (C-1) obtained in Synthesis Example 2, in a toluene solution with 62% non-volatile components. • Maleimide resin (C-2): Maleimide resin (C-2) obtained in Synthesis Example 3, in a toluene solution with 62% non-volatile components. • MIR-5000-60T: Maleimide resin represented by the following formula, manufactured by Nippon Kayaku Co., Ltd., toluene solution with 60% non-volatile components.
[0340] [ka]
[0341] • Maleimide resin (C-4): Maleimide resin represented by the following formula (C-4) (wherein X is a divalent group represented independently by one of the following formulas (a') to (d'), where m≧0 and n≧1. In formulas (a') to (d'), * represents a bond to the nitrogen atom of the maleimide group, and m, n, p, and q are integers of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, respectively. Bonds shown by dashed lines represent carbon-carbon single bonds or carbon-carbon double bonds. However, if a bond shown by a dashed line is a carbon-carbon double bond, the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is one less than the number shown in formulas (a') to (d').)
[0342] [ka]
[0343] (C2) Maleimide resins that do not have aromatic rings, or have aromatic rings, but the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. • BMI-689: An N-alkylbismaleimide manufactured by Designer Molecules Inc., having a skeleton derived from a dimeramine with the structure represented by the following formula (C2-2).
[0344] [ka]
[0345] • SLK-1500-T80: A toluene solution containing 80% non-volatile components, containing an N-alkylbismaleimide having a skeleton derived from a dimeramine with the structure represented by the following formula (C2-1), manufactured by Shin-Etsu Chemical Co., Ltd.
[0346] [ka] (In equation (C2-1), the mean value of n is 1.3.)
[0347] (D) Phenolic resins (excluding those having a triazine skeleton). HCA-HQ-HST: Hydroxyl group equivalent 162g / eq., phosphorus content 10% by mass, manufactured by Sanko Co., Ltd., 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide
[0348] [ka]
[0349] • KA-1160: Hydroxyl group equivalent 117 g / eq., manufactured by DIC Corporation, novolac-type phenolic resin represented by the following formula (D-1-2) (softening point 81-90°C) • KA-1163: Hydroxyl group equivalent 118 g / eq., manufactured by DIC Corporation, novolac-type phenolic resin represented by the following formula (D-1-2) (softening point 105~115°C) • KA-1165: Hydroxyl group equivalent 119 g / eq., manufactured by DIC Corporation, novolac-type phenolic resin represented by the following formula (D-1-2) (softening point 117~130°C)
[0350] [ka]
[0351] GPH-65: Hydroxyl group equivalent 201 g / eq., manufactured by Nippon Kayaku Co., Ltd., biphenyl aralkyl type phenolic resin
[0352] [ka]
[0353] • SN-395: Hydroxyl group equivalent 110g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd., naphthol aralkyl type phenolic resin
[0354] [ka]
[0355] • SN-485: Hydroxyl group equivalent 215g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd., naphthol aralkyl type phenolic resin
[0356] [ka]
[0357] • SN-4110V: Hydroxyl group equivalent 300g / eq., manufactured by Nippon Steel Chemical & Material Co., Ltd.
[0358] [ka]
[0359] • FATC809: Hydroxyl group equivalent 1250g / eq., manufactured by Gun-ei Chemical Industry Co., Ltd.
[0360] [ka]
[0361] (E) Inorganic filler • SO-C2: Spherical silica manufactured by Admatex, with an average particle size of 0.5 μm, surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573," N-phenyl-3-aminopropyltrimethoxysilane). • LHP-208: Hollow silica manufactured by Ube Eximo Co., Ltd., with an average particle size of 0.5 μm, porosity of 50% by volume, and surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573", N-phenyl-3-aminopropyltrimethoxysilane). • MGH-005: Hollow silica manufactured by Taiheiyo Cement Corporation, with an average particle size of 1.6 μm, porosity of 80% by volume, and surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573," N-phenyl-3-aminopropyltrimethoxysilane).
[0362] (F) Other hardening agents • V-03: Active group equivalent 216g / eq., manufactured by Nisshinbo Chemical Co., Ltd., carbodiimide-based curing agent LA-3018-50P: Hydroxyl group equivalent 151 g / eq., manufactured by DIC Corporation, triazine skeleton-containing phenolic resin, 2-methoxypropanol solution with 50% non-volatile components.
[0363] (G) Organic filler • EXL-2655: A core-shell type cushion filler containing rubber components, manufactured by Dow Corporation.
[0364] (H)Thermoplastic resin • YX7553BH30: A phenoxy resin mixed solution containing 30% non-volatile MEK and cyclohexanone, manufactured by Mitsubishi Chemical Corporation.
[0365] (I) Curing accelerator • 1B2PZ: Imidazole-based curing accelerator (1-benzyl-2-phenylimidazole), manufactured by Shikoku Chemicals Co., Ltd. • BT-120: Triazole-based curing accelerator (1,2,3-benzotriazole), manufactured by Johoku Chemical Industry Co., Ltd.
[0366] <Test Example 1: Measurement of Dielectric Loss Tangent> (1-1) Preparation of evaluation film A glass cloth-based epoxy resin double-sided copper-clad laminate (Panasonic R5715ES, 0.7 mm thick, 255 mm square) was placed on the untreated side of a PET film (50 μm thick, 240 mm square) treated with Lintec's "1010" release agent, and the four sides were fixed with polyimide adhesive tape (10 mm wide) (hereinafter sometimes referred to as "fixed PET film").
[0367] The resin compositions obtained in the examples and comparative examples were applied to the release-treated surface of the "fixed PET film" using an applicator so that the thickness of the dried resin composition layer was 40 μm, and dried at 90°C for 3 minutes. Resin sheet A, consisting of a PET film and a resin composition layer, was obtained by removing it from the glass cloth substrate epoxy resin double-sided copper-clad laminate. Resin sheet B was obtained by the same manufacturing method as resin sheet A, except that the coating thickness of the resin composition was changed so that the thickness of the dried resin composition layer was 27.5 μm.
[0368] (1-2) Preparation of hardened samples for evaluation Resin sheet A was placed in an oven at 190°C and the resin composition layer was heat-cured for 90 minutes under curing conditions. After heat curing, the PET film was peeled off to obtain a sheet-like cured product. The obtained cured product is referred to as the "evaluation cured product".
[0369] (1-3) Measurement of dielectric loss tangent The cured material for evaluation was cut to obtain test specimens measuring 30 mm in width and 40 mm in length. The dielectric loss tangent Df of these test specimens was measured using the split-cylinder method with an Agilent Technologies HP8362B at a measurement frequency of 10 GHz and a measurement temperature of 90°C. Measurements were performed on two test specimens, the average value was calculated, and the results were evaluated according to the following criteria. "×": Dielectric loss tangent is 0.0032 or higher "△": Dielectric loss tangent is 0.0030 or greater and less than 0.0032. "○": Dielectric loss tangent is less than 0.0030
[0370] <Test Example 2: Measurement of Dielectric Loss Tangent Increase> For evaluation cured samples with thicknesses of 25 μm and 40 μm, the dielectric loss tangent Df was measured using the procedure in Test Example 1, and the rate of increase in dielectric loss tangent in thin films was calculated according to the following formula. Furthermore, evaluation was performed according to the following criteria. Dielectric loss tangent increase rate (%) = ((Df of 25 μm evaluation cured material / Df of 40 μm evaluation cured material) - 1) × 100 "×": Dielectric loss tangent increase rate is 5% or more "○": Dielectric loss tangent increase rate is less than 5%
[0371] <Test Example 3: Evaluation of Film Stability> From the resin sheet A obtained in Test Example 1, only the resin composition layer was peeled off, and a measurement pellet (18 mm in diameter, 1.3 g) was obtained by compressing it in a mold.
[0372] Using a dynamic viscoelasticity analyzer (UBM "Rheosol-G3000"), 1.3g of measurement pellets were heated from a starting temperature of 70°C to 200°C at a heating rate of 5°C / min using an 18mm diameter parallel plate. The dynamic viscoelasticity was measured under measurement conditions of a 2.5°C temperature interval, a frequency of 1Hz, and a strain of 5deg. After measuring the dynamic viscoelasticity, a graph was created with temperature on the x-axis and melt viscosity on the y-axis, and the minimum melt viscosity (MV) was calculated. 0h ) was calculated.
[0373] Next, under conditions of 23°C and 40-45% humidity, the resin sheet A obtained in Test Example 1 was left to stand for 72 hours from T0, when the temperature of the resin composition layer reached 23°C. After standing, only the resin composition layer was peeled off the resin sheet and compressed in a mold to obtain a measurement pellet (18 mm in diameter, 1.3 g). After similarly measuring the dynamic viscoelastic modulus, a graph was created with temperature on the x-axis and melt viscosity on the y-axis, and the minimum melt viscosity (MV) was calculated. 72h ) was calculated.
[0374] MV obtained from the above measurements 0h and MV 72h Based on the values, the stability of the melt viscosity was evaluated according to the following criteria. The stability of the film can be evaluated based on the stability of the melt viscosity. (Evaluation criteria for the stability of melt viscosity) "○": 1.00≦MV 72h / MV 0h The relationship <1.50 is satisfied. "×": MV 72h / MV 0h <1.00, or MV 72h / MV 0h The result is ≥1.50.
[0375] <Test Example 4: Evaluation Test of Adhesion to Copper Substrate> (4-1) Lamination of resin sheet B onto inner layer substrate As an inner layer circuit board with copper foil on both sides, a glass cloth substrate epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") was prepared. The surfaces of the copper foil on both sides of the inner layer circuit board were roughened using MEC's "CZ8101" (copper etching amount 1.0 μm).
[0376] The resin sheet B manufactured in Test Example 1 was laminated on both sides of the inner circuit board using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. 2-stage build-up laminator "CVP700") so that the resin composition layer of resin sheet B was bonded to the inner circuit board. Lamination was performed by reducing the pressure to 13 hPa or less for 30 seconds, followed by pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet B was heat-pressed at atmospheric pressure, 100°C, and a pressure of 0.5 MPa for 60 seconds to smooth it. After that, the support film (PET film) was peeled off to obtain an "intermediate multilayer body I" containing the resin composition layer / inner circuit board / resin composition layer in that order.
[0377] (4-2) Lamination of copper foil A copper foil with a glossy surface (35 μm thick, manufactured by Mitsui Mining & Smelting Co., Ltd., "3EC-III") was prepared. The glossy surface of this copper foil was roughened by etching with a micro-etching agent (manufactured by MEC Corporation, "CZ8101") to a copper etching depth of 1 μm. The copper foil obtained in this way is called "roughened copper foil".
[0378] This roughened copper foil was laminated on both sides of the intermediate multilayer I such that the roughened surface of the roughened copper foil was bonded to the resin composition layer of the intermediate multilayer I. This lamination was carried out under the same conditions as the lamination of resin sheet B to the inner substrate described above. As a result, an "intermediate multilayer II" was obtained, containing roughened copper foil / resin composition layer / inner substrate / resin composition layer / roughened copper foil in this order.
[0379] (4-3) Thermocuring of the resin composition layer The obtained intermediate multilayer II was placed in a 130°C oven and heated for 30 minutes, then transferred to a 170°C oven and heated for another 30 minutes. Next, the intermediate multilayer II was removed from the oven and left in a room temperature atmosphere, and then placed in a 190°C oven and heated for an additional 90 minutes. This caused the resin composition layer to heat-cur, yielding "evaluation substrate A" containing, in this order, roughened copper foil / insulating layer as a cured product of the resin composition layer / inner layer substrate / insulating layer as a cured product of the resin composition layer / roughened copper foil. In evaluation substrate A, the roughened copper foil corresponds to the conductive layer.
[0380] (4) Measurement of adhesion strength with the conductor layer Using the obtained evaluation substrate A, the peel strength between the roughened copper foil and the insulating layer was measured. This peel strength measurement was performed in accordance with JIS C6481. Specifically, the peel strength was measured by the following procedure.
[0381] A rectangular section measuring 10 mm wide and 100 mm long was cut into the roughened copper foil of evaluation substrate A. One end of this rectangular section was peeled off and grasped with a gripper (TSE Corporation's Autocom type testing machine "AC-50C-SL"). A 35 mm length section of this rectangular area was peeled vertically, and the load (kgf / cm) during this peeling was measured as the peel strength. The above peeling was performed at a speed of 50 mm / min at room temperature.
[0382] A higher peel strength indicates better adhesion to the underlying copper. Therefore, the measured peel strength was evaluated based on the following criteria. "○": Peel strength of 0.5 kgf / cm or higher "×": Peel strength is less than 0.5 kgf / cm
[0383] <Test Example 5: Evaluation Test of Adhesion to Substrate Copper After HAST> In Test Example 4, the samples after substrate adhesion measurement were subjected to a 100-hour accelerated life test (HAST) using an accelerated life testing apparatus (PM422, manufactured by Kusumoto Chemical Co., Ltd.) at 130°C and 85%RH. Subsequently, the peel strength after HAST was determined in the same manner as in Test Example 4 and evaluated based on the following criteria. "○": Peel strength of 0.35 kgf / cm or higher "△": Peel strength is 0.25 kgf / cm or more and less than 0.35 kgf / cm "×": Peel strength is less than 0.25 kgf / cm
[0384] As shown in Tables 1 to 8, Examples 1 to 32, which contained (A) epoxy resin, (B) activated ester resin, (C1) maleimide resin having aromatic rings and a ratio of dimeramine skeletons to aromatic rings (dimeramine / aromatic ring) of 0.25 or less, (C2) maleimide resin without aromatic rings, or having aromatic rings and a ratio of dimeramine skeletons to aromatic rings (dimeramine / aromatic ring) greater than 0.25, (D) phenol resin (excluding those having a triazine skeleton), and (E) inorganic filler, simultaneously achieved excellent dielectric loss tangent, suppression of dielectric loss tangent increase rate, excellent film stability, and excellent adhesion to the substrate copper. On the other hand, Comparative Example 1, which did not contain component (D), had a high dielectric loss tangent increase rate and was not at a satisfactory level. Comparative Example 2, which contained a triazine skeleton-containing phenol resin instead of component (D), did not achieve a satisfactory level of film stability. In Comparative Examples 3 and 5, which did not contain component (C2), the adhesion to the copper substrate was not at a satisfactory level. In Comparative Examples 4 and 5, which did not contain component (C1), the dielectric loss tangent was not at a satisfactory level. Furthermore, in Comparative Example 6, which did not contain (B) activated ester resin, the dielectric loss tangent was not at a satisfactory level. In Comparative Example 7, which did not contain (A) epoxy resin and (B) activated ester resin, the adhesion to the copper substrate was not at a satisfactory level.
Claims
1. (A) Epoxy resin, (B) Activated ester resin, (C) Maleimide resin, (D) Phenolic resins (excluding those having a triazine skeleton), and (E) inorganic filler; A resin composition containing, A resin composition comprising a maleimide resin in which component (C) has an aromatic ring and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is 0.25 or less, and a maleimide resin in which component (C2) does not have an aromatic ring, or has an aromatic ring and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.
25.
2. The resin composition according to claim 1, wherein the ratio of the total number of moles of active groups of component (B) to the total number of moles of active groups of component (A) [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.9 or less.
3. The resin composition according to claim 1, wherein the ratio of the total number of moles of active groups of component (B) to the total number of moles of active groups of component (A) [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.2 or more.
4. The resin composition according to claim 1, wherein the content of component (C) is 1 to 15% by mass, when the nonvolatile components in the resin composition are considered to be 100% by mass.
5. The resin composition according to claim 1, wherein the mass ratio of component (C1) to component (C2) [(C1) component / (C2) component] is 0.1 to 100.
6. The resin composition according to claim 1, wherein component (C2) comprises a maleimide resin represented by the following formula (C2-1). 【Chemistry 1】 (In the formula, n represents a non-negative integer, and * represents a combination.)
7. The resin composition according to claim 1, wherein component (D) has an aromatic ring other than a phenol skeleton.
8. The resin composition according to claim 1, wherein component (D) has two or more phenolic hydroxyl groups in one molecule.
9. The resin composition according to claim 1, wherein component (D) does not have an alkyl group having 3 or more carbon atoms.
10. The resin composition according to claim 1, wherein component (D) is a phenolic resin whose constituent atoms are selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms.
11. The resin composition according to claim 1, wherein component (D) is a phenolic resin having carbon atoms, hydrogen atoms, oxygen atoms, and phosphorus atoms as constituent atoms.
12. The resin composition according to claim 1, wherein the content of component (D) is 0.1 to 10% by mass, when the non-volatile components in the resin composition are taken as 100% by mass.
13. Furthermore, the resin composition according to claim 1, further comprising (G) an organic filler.
14. Furthermore, the resin composition according to claim 1, further comprising (H) a thermoplastic resin.
15. Furthermore, the resin composition according to claim 1, further comprising (I) a curing accelerator.
16. A resin composition according to any one of claims 1 to 15, for use as an insulating layer for a circuit board.
17. A resin sheet comprising a support and a layer of the resin composition according to any one of claims 1 to 15 provided on the support.
18. The resin sheet according to claim 17, wherein the support is a thermoplastic resin film or a metal foil.
19. A cured product of the resin composition according to any one of claims 1 to 15.
20. A circuit board comprising an insulating layer having a cured product of the resin composition according to any one of claims 1 to 15.
21. A semiconductor device comprising the circuit board described in claim 20.
Citation Information
Patent Citations
Epoxy resin composition
JP2010090238A